A machine learning-based dual system coupling model of catalytic-gasification: a calcium-based case study with mechanistic interpretability - Yadong Ge; HongRu Li; Zaixin Li; Zhi Wang; Xiaoqiang Cui; Beibei Yan; Junyu Tao; Zhanjun Cheng; Ningbo Gao (Bioresource Technology, 2027)

Human YTHDC2 mutations disturb RNA homeostasis of oocytes and early embryos - Wei Su; Yang Wang; Jiaqi Sun; Changlong Zhang; Changjian Yin; Ying Cui; Xiaolei Chen; Bohan Yang; Shigang Zhao; Keliang Wu; Ge Lin; Zi-Jiang Chen; et al. (Human Genetics, 2026)

Integrating genomic evolution and reported outbreak occurrence in foot-and-mouth disease in Asia: Cross-border lineage connectivity and exploratory prediction of reported outbreak occurrence - Xiaoyu Ge; Yize Li; Jiaxuan Li; Yanping Jiang; Wen Cui; Xiaona Wang; Lijie Tang (Preventive Veterinary Medicine, 2026)

Mechanism of sandstone breaking by Laval annular air-shielded water jet crushing in submerged environment and the improvement of long target distance performance - Zhaolong Ge; Mengting Wang; Binbin Ge; Xuanyi Chen; Hongwei Zhang; Xiaotian Wang; Rongzheng Ge; Jinming Cui; Sen Wen (International Journal of Rock Mechanics and Mining Sciences, 2026)

Changes in the gut microbiome and neurotransmitters induced by mancozeb - Hongnuo Ge; Minrong Cui; Yinuo Liu; Xiaomao Wu; Chenyu Huang; Luqing Zhang; Hua Fang (Environmental Pollution, 2026)

Toward tailoring vortex synergy for predictive vortex-induced vibrations suppression in bridge girders - Shuaikuang Chen; Chuanxin Hu; Lin Zhao; Wei Cui; Qiang Zhou; Yaojun Ge (Engineering Structures, 2026)

Enterococcus in herbal fermentation: a genus-specific perspective on enzymatic capability, biotransformation outcomes and safety - Jiafei Tang; Shuo Zhang; Gui Xu; Mengxiao Cui; Xiutong Ge; Hui Gao; Fan Zhang (Archives of Microbiology, 2026)

BlOFP1 is associated with reduced secondary cell wall formation and interacts with BlKNOX9 and BlBLH9 in Betula luminifera - Fei Ni; Xian-Ge Hu; Hebi Zhuang; Fuqiang Cui; Yousry A. El-Kassaby; Erpei Lin; Huahong Huang (Plant Science, 2026)

Spatial patterns of modern pollen deposition as a basis for paleoecological interpretation in deep lakes: Insights from Fuxian Lake, Southwest China - Fan Xu; Sidan Cui; Jinhao Dong; Yawen Ge; Wenlei Luo; Lixin Xu; Yuecong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Purification reshapes systemic exposure and immunomodulation-mediated antiviral responses of licorice triterpenoids - Zhongyuan Li; Miaomiao Liu; Ge Qu; Guige Hou; Jipeng Wang; Yukui Ma; Qinghua Cui (Food Research International, 2026)

Climate and soil properties drive microplastic enrichment patterns in agricultural soils across a multi-country survey - Martine Graf; Michaela K. Reay; Yingming Sun; Fan Ding; Siyang Ren; Kai Wang; Changrong Yan; Shitong Li; Tida Ge; Xuejun Liu; Ruimin Qi; Jixiao Cui; et al. (Environmental Pollution, 2026)

Correction: Obesity Worsens Arsenic Trioxide-Induced Myocardial Toxicity and Its Protection by Metallothionein - Tingwen Ge; Lei Qian; Aiwen Li; Qiang Guo; Qiuju Liu; Jiuwei Cui (Cardiovascular Toxicology, 2026)

Precisely regulating the microenvironment towards robust active site for antibiotics degradation via Fenton-like reaction - Jiahao Cui; Wei Jian; Di Meng; Kun Wang; Jiaran Yao; Lina Li; Zijian Xu; Rile Ge; Junhu Wang; Jikun Li; Wonyong Choi; Yubao Zhao (Water Research, 2026)

Expression and functional role of NAD(P)H:quinone oxidoreductase 1 (NQO1) in glycidyl methacrylate-induced malignant transformation of lung epithelial cells - Xintong Liu; Hongjiao Wu; Yishuang Cui; Yexuan Liu; Ziqing Liu; Jiawen Sun; Yanlei Ge; Ye Jin; Junqing Gan; Weinan Yao; Yanna Bi; Guogui Sun (Toxicology and Applied Pharmacology, 2026)

Evaluating the collective effects of vertical and ground greening on microclimate and energy consumption in a high-density building array - Dongjin Cui; Ruikun Ge; Xiaolong Zheng; Guozhu Liang; Jian Hang; Cheuk Ming Mak (Sustainable Cities and Society, 2026)

TBBPA-induced insulin reduction in two generations of marine medaka (Oryzias melastigma) with calcium signaling as a key event - Teng Wang; Yi Ge; Jinghe Li; Yanxin Qiao; Yingqi Tang; Xiaoying Cui; Jin Yong Lee; Zhengyan Li (Environmental Pollution, 2026)

Cyclic behaviour of plate-monopile and bucket-monopile hybrid foundation in sand - Yukun Ma; Sanchari Mondal; Ge Cui; Muhammad Aleem; Subhamoy Bhattacharya; Liang Cui (Computers and Geotechnics, 2026)

Solvent-gradient coordination design of LiNO3-based electrolytes for anode-free lithium metal batteries - Shifei Huang; Yuan Liu; Yao Lv; Guohuang Kang; Jiang Xu; Jia Cui; Yufeng Zhao; Wei Yan; Jiujun Zhang; Shanhai Ge (Chemical Engineering Journal, 2026)

Bismuth-embedded hard carbon derived from Solidago canadensis toward sodium-ion batteries - Jiacheng Shen; Liang Liu; Hong Cui; Yiting Dai; Ge Lin; Yuanzhe Wang; Ziyao Zhang; Jiantie Xu (Chemical Engineering Journal, 2026)

Rapid prediction of wind field in street canyons with infrastructure elements using neural operators - Guozhu Liang; Ruikun Ge; Dongjin Cui; Jian Hang; Gang Hu; Cheuk Ming Mak (Urban Climate, 2026)

Spatial decoupling of electron donation and oxygen capture for efficient endogenous oxygen-driven electrosynthesis of 1O2 in water remediation - Xifeng Lu; Pei Su; Jingxuan Zhao; Xuedong Du; Ge Song; Boxuan Cui; Kexin Chen; Qingrui Zhang; Minghua Zhou (Science Bulletin, 2026)

Loss of eIF3m aggravates myocardial ischemia/reperfusion injury via enhancing nitrative damage and inhibiting glycolytic reprogramming - Zilun Wei; Yongchao Zhao; Daile Jia; Rifeng Gao; Weidong Xiong; Xiaolei Sun; Xinyu Weng; Bowen Liu; Shuai Song; Wei Luo; Jian Cui; Kai Hu; et al. (Science Bulletin, 2026)

Dynamic evolution mechanism and quantitative parameter regulation strategy of water jet ice-breaking - Xuanyi Chen; Zhaolong Ge; Binbin Ge; Hongwei Zhang; Jianming Shangguan; Rongzheng Ge; Jinming Cui; Sen Wen; Mengting Wang (Ocean Engineering, 2026)

One-shot quantification of 313 PPCPs and pesticides in bovine milk by modified-QuEChERS-UHPLC-MS/MS - Liang Zhao; Yuanyuan Luo; Mengxuan Zhu; Xiaowei Li; Saiwa Liu; Jingjing Du; Lirui Ge; Jian Xu; Kexin Cui; Yu Ga; Shuwen Wang; Jingyu Liu; et al. (Food Chemistry, 2026)

Excavation Face Stability of Underwater Shield Tunnels in Lower Dense and Upper Loose Strata - Fei Jia; Chuang Wang; Pengfei Li; Xiaopu Cui; Qing Xu; Zhaoguo Ge (Geotechnical and Geological Engineering, 2026)

Seismicity Analysis of the Beijing Area from an Enhanced Long-Term Earthquake Catalog - Huiying Ge; Hongyi Li; Tongli Wang; Shengzhong Zhang; Bowen Cui (Journal of Earth Science, 2026)

Energy Absorption Model and Mechanism of Abrasive Water Jet Cutting on Sandstone Under Stress Based on Cutting Striations - Yiyu Lu; Houhan Pu; Qinglin Deng; Zhaolong Ge; Zhuolin Shi; Jianming Shangguan; Yuhuai Cui; Zhi Yao; Yunliang Wang (Rock Mechanics and Rock Engineering, 2026)

Real-time sick fish detection system for aquaculture based on edge computing - Duanrui Wang; Fan Ge; Rui Xu; Xingyue Zhu; Hongjian Lv; Dianting Zeng; Meng Wu; Jiyang Yu; Weijian Cui; Qiwei Qin; Shaowen Wang; Yi Shi; et al. (Aquaculture, 2026)

Pear PbrPRKs regulate pollen tube growth via modulation of apical actin and reactive oxygen species homeostasis - Lan Xu; Yuzhen Qian; Yusheng Xu; Haoran Wu; Juan Ma; Jitao Ge; Yuqian Wang; Kaijing Zhang; Yihu Sui; Xueping Zhang; Jingjing Qian; Shuangshuang Jia; et al. (Plant Science, 2026)

Emitter flow rate of drip irrigation regulates the distribution and bioaccumulation of typical PPCPs in reclaimed wastewater-irrigated soil-plant systems - Jing Jin; Songjing Li; Erping Cui; Chao Hu; Shengshu Li; Zhenchao Zhou; Bingjian Cui; Chuncheng Liu; Junying Chen; Ge Gao; Xiangyang Fan (Journal of Environmental Sciences, 2026)

Synergistic Mo2C/MoO2 hybridization in sucrose-derived hard carbon spheres for sodium-ion batteries - Hong Cui; Liang Liu; Jiacheng Shen; Ge Lin; Yiting Dai; Yuanzhe Wang; Yue Tang; Jiantie Xu (Chemical Engineering Journal, 2026)

Reconstructing 150 years of land-use history in an alpine-deep lake: A high-resolution multi-proxy sediment record from Fuxian Lake, China - Fan Xu; Sidan Cui; Jinhao Dong; Sihan Li; Yawen Ge; Wenlei Luo; Yuecong Li (CATENA, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

New Insights into the Aquatic Photochemistry of Sulfonamide Antibiotics: Apparent Photolysis, Toxicity Evolution and Mechanisms - Linke Ge; Jiahui Wang; Andrew Sweetman; Zhixuan Zheng; Peng Zhang; Nannan Cui (Water, Air, & Soil Pollution, 2026)

Dynamic Threshold Pressure Gradient Model of CO2 Injection into Coal Seams Based on Fractal Theory - Jing Han; Zhe Zhou; Zhaolong Ge; Jianming Shangguan; Jinming Cui (Rock Mechanics and Rock Engineering, 2026)

The VP1 protein of foot-and-mouth disease virus: Bridging pathogenicity and control strategies - Yize Li; Xiaoyu Ge; Jing Yang; Jiaxuan Li; Wen Cui; Xiaona Wang; Lijie Tang (The Veterinary Journal, 2026)

Early-life and lifelong exposure to environmentally relevant enrofloxacin reorganizes a proteobacteria-centered gut-lipid-resistome steady state in marine medaka - Ziyi Guo; Zheyu Wang; Yaxin Liu; Meiru Wang; Hongyue Ma; Ziwei Wang; Siyuan Zhang; Yidan Chang; Hezi Ge; Chenglu Li; Hui Yang; Hui Miao; et al. (Journal of Hazardous Materials, 2026)

Integrated metabolomics and GC-IMS analysis to reveal the flavor formation of Mactra veneriformis during combined hot-air drying with boiling pretreatment - Jing Ge; Guifang Tian; Yifan Cui; Jiayi Wang; Zhongxuan Wang; Yaxin Sang (Food Chemistry, 2026)

Exploring the multiple photochemical behaviors of ionizable EDCs in aquatic environments: Kinetics, intermediates, and toxicity evolution - Linke Ge; Shijing Yang; Nannan Cui; Chang-Er Chen; Xiaojia Che; Peng Zhang (Environmental Research, 2026)

Interfacial polymerization-transfer governs C/N fate during peroxymonosulfate activation on oxygen-vacancy-rich CoFe-LDH - Li Cui; Shanshan Deng; Yujia Zhang; Sai Zhang; Yu Ge; Ruoding Wang; Zhonglong Yin; Guandao Gao; Weiben Yang (Chemical Engineering Journal, 2026)

Recycling spent lithium-ion batteries as high-performance catalysts for peracetic acid activation toward rapid degradation of organic pollutants - Ge Li; Yujie Cheng; Yufei Wu; Yuhao Tian; Bowen Yang; Haoran Chen; Guosen Zhang; Zhengqian Liu; Yuhong Cui; Jun Ma; Pengchao Xie (Chemical Engineering Journal, 2026)

A benzopyran-based near-infrared fluorescent probe with a large stokes shift for visualizing cysteine dynamics in hepatic ischemia-reperfusion injury and tumor tissues - Feng Pei; Zhipeng Sai; Chaochu Cui; Xiaoyu Wang; Pengcheng Zhang; Yao Zhao; Yuhan Hu; Zhijun Yang; Chunpo Ge (Chemico-Biological Interactions, 2026)

Flexible SERS tape: A plasmonic hybrid of AuNPs and layered K2Ti8O17 nanowire network for on-site detection of pesticide residues - Lin Xu; Mingru Cui; Zhongqi Ge; Ruikang Zou; Cong Wang; Pengfei Ni; Xi Huang; Bo Zhong; Lijuan Wang (Analytica Chimica Acta, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Association Between Lead Exposure and Anthropometric Indicators in School-aged Children: A Longitudinal Study - Xiangju Wu; Yang Zhou; Linhong Li; Jieying Gao; Rongchang Xiao; Qian Yang; Meng Wu; Siyan Ye; Chengpeng Cui; Peng Lin; Ruifeng Luo; Ge Yan; et al. (Biological Trace Element Research, 2026)

Adaptive VP1 sites 93 and 97 modulate antigenic evolution and receptor binding of Senecavirus A: Phylogenetic analysis and validation with recombinant viruses - Jing Yang; Zhiliang Zhang; Weijia Sha; Mingyue Peng; Yize Li; Xiaoyu Ge; Jiaxuan Li; Wen Cui; Yanping Jiang; Xiaona Wang; Lijie Tang (Veterinary Microbiology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Three-dimensional identification of dominant atmospheric pollutants and their sensitivity to soil moisture in northwestern china urban agglomerations - Jinglong Li; Jiawen Cui; Yonghui Wang; Peng Wu; Lu Zhang; Xiangyu Ge; Qing He; Xingbin Xu (Journal of Environmental Sciences, 2026)

Characteristics, source apportionment, and secondary transformation of volatile organic compounds during different seasons at an urban site in southeast China - Xiaoming Liu; Jie Zhang; Zhengyu Lu; Qingzhi Ge; Shekou Wang; Donglin Chen; Mindong Chen; Yan Cui (Journal of Environmental Sciences, 2026)

Increased heterogeneity of sedimentary potential silicate-solubilizing bacterial communities caused by cascade damming reduces community complexity but promotes stability - Juan Chen; Qihao Nie; Chao Wang; Peifang Wang; Yuansheng Zhu; Ge Cui; Han Gao; Bo Zhang; Shunqing Zhang (Journal of Environmental Sciences, 2026)

Gender-specific association between PM2.5 exposure and cognitive function in middle-aged and elderly chinese: Evidence from CHARLS - Man Quan; Jing Cui; Yukui Chen; Jiayi Hao; Chenshu Ge; Xiaomei Li; Juan Wang; Duolao Wang; Leilei Pei; Yijun Kang; Lu Ye (Air Quality, Atmosphere & Health, 2026)

Novel biodiversity and biogeography insights of filamentous Bangiales (Rhodophyta) from China - Yan-De Wang; Yin-Yin Deng; Cui-Cui Tian; Han-Ru Ge; Wei Zhou; Nan-Jing Ji; Li-En Yang (Algae, 2026)
The taxonomy of filamentous Bangiales was challenging due to its plastic and simple morphology. Molecular approaches play a significant role in revealing cryptic biodiversity and resolving phylogenetic relationships. Nonetheless, the biodiversity of filamentous Bangiales in many regions, including China, has not been thoroughly investigated yet using updated methods. In this study, we investigated the biodiversity of filamentous Bangiales in China, employing a more comprehensive and detailed sampling approach. The rbcL and 18S gene sequences (partial or complete) of 49 specimens collected from 37 sites were obtained. Phylogenetic analysis resolved these specimens into four clades, including Bangia, ‘Bangia’ 1, ‘Bangia’ 2, and Pseudoganglia. Seven putative species were delineated using empirical methods, including Automatic Barcode Gap Discovery (ABGD), General Mixed Yule Coalescent (GMYC), and Bayesian Poisson tree processes (bPTP), as well as genealogical analysis. Among them, four were species previously reported, two were cryptic species, and the other was a new record in China. The distribution of these molecularly delineated species was mapped along China’s coastline. Similar to the bladed Bangiales, antitropical, transoceanic, and thermal-gradient distribution patterns were also observed for filamentous Bangiales on a global scale. The ancestral region was retraced by incorporating species data from China into existing datasets using BioGeoBEARS with BAYAREALIKE + J as the best-supported model. Under this model, East Asia shows the highest marginal probability as the ancestral area for the crown clade, though uncertainty remains across alternative regions. A most parsimonious expansion scenario of Bangiales from east Gondwana to other regions of the world was proposed.

Effect of Dry–Wet Cycling on the Abrasive Water Jet Cutting Performance of Green Sandstone - Zhaolong Ge; Zhuolin Shi; Qinglin Deng; Jianming Shangguan; Zhi Yao; Yuhuai Cui; Houhan Pu (Rock Mechanics and Rock Engineering, 2026)

Visualization study on combustion characteristics of direct-injection methanol ignited by micro-injection diesel in a hydrogen-rich syngas atmosphere - Yuanyou Tang; Wuqiang Long; Zhizhuo Dai; Zechuan Cui; Yang Wang; Ge Xiao; Pengbo Dong; Hua Tian (Fuel, 2026)

Robust oxygen vacancy surfaces induce chemical bonding interfaces of Bi2Sn2O7/Bi2MoO6 S-scheme heterojunction with asymmetric adsorption sites for efficient photocatalytic nitrogen fixation - Yongli Li; Xin Kong; Rui Bao; Liang Liu; Zhenhua Ge; Feng Liu; Hao Cui; Jianhong Yi (Chemical Engineering Journal, 2026)

Cytoplasmic-nuclear remote suppression of c-MYC induces cell cycle arrest and enhances radiotherapy sensitivity in liver cancer via biohybrid platelets - Lin Xiao; Fei Ge; Qinyu Ji; Rui Ji; Yan Wang; Shaoqing Ju; Ming Cui; Donglin Xia; Rongrong Jing (Chemical Engineering Journal, 2026)

Impact of Madden–Julian Oscillation on the forecast of marine heatwaves in the southeastern tropical Indian ocean - Zhanxian Cui; Yuanlong Li; Yangke Liu; Qing Bao; Lei Zhang; Kai Ge; Fan Wang (Climate Dynamics, 2026)

Asymmetric Propagation of Hydraulic Fractures in Coal–Rock Composite Formations: Insights Based on Stress Sensitivity of Coal - Zhaolong Ge; Changzheng Lu; Qinglin Deng; Zhe Zhou; Shuo Dai; Jing Han; Jinming Cui (Rock Mechanics and Rock Engineering, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Evidence of heterogeneity in the mantle source of Quaternary Naozhou Island basalts from REEs and Sr-Nd-Pb isotopes - Cui Xiao-Ge; Li Zhi-Hua; Xie Shi-Xiong; Yang Wen-Jian; Wang Ming-Qiu; Cheng Liu-San; Gao Cai-Xia; Jiang Hong-Liang (Lithos, 2026)

Mechanism of physicochemical changes in potato starch gel induced by citric acid-autoclaving for texture improvement and resistant starch formation - Linlin Cui; Xinzhu Wang; Shuhan Ge; Xia Li; Yu Wang; Bo Nan; Zhicheng Zhang; Yuhua Wang (Food Chemistry, 2026)

A novel partitioned anaerobic membrane bioreactor integrated with ferromagnetic biochar for complex pesticide wastewater: Mass balance, membrane fouling mitigation, energy footprint, and life cycle assessment - Yifan Wang; Liwen Jiang; Dongxue Hu; Shiming Cui; Bei Jiang; Hui Ge; Shuya Zhuang; Jitao Yan; Zihan Wang; Pengcheng Zhang; Zhaobo Chen (Environmental Research, 2026)

Experimental Study on the Jet Mechanism and Rock Breaking Performance of Polyacrylamide Solution Jet - Hongwei Zhang; Zhaolong Ge; Jinming Cui; Sen Wen; Binbin Ge (Rock Mechanics and Rock Engineering, 2026)

Obesity Worsens Arsenic Trioxide-Induced Myocardial Toxicity and Its Protection by Metallothionein - Tingwen Ge; Lei Qian; Aiwen Li; Qiang Guo; Qiuju Liu; Jiuwei Cui (Cardiovascular Toxicology, 2026)

Chemical characteristics of fine aerosols and associated speciated organic compounds in summer Nanjing, China - Yuanjie Shan; Daoming Li; Shijie Cui; Jiukun Xian; Yunjiang Zhang; Junfeng Wang; Haiwei Li; Ming Wang; Yun Wu; Xinlei Ge (Journal of Environmental Sciences, 2026)

Study on the origin identification of Anji Baicha based on mineral elements - Yuanyuan Zhu; Yaning Lu; Chuanjian Cui; Ge Jin; Ying Xu; Xiaochun Wan; Ruyan Hou (Food Chemistry, 2026)

Characteristics of Submicron Aerosols (PM1) in a Yangtze River Delta Megacity: Composition, Sources, and Light Absorption - Shiyue Yang; Haifeng Meng; Ning Zhang; Shijie Cui; Yuanjie Shan; Yu Huang; Yunlong Xu; Chongchong Zhang; Xinlei Ge; Mindong Chen; Junfeng Wang (Advances in Atmospheric Sciences, 2026)

Duxseal boundary effects on static and dynamic responses in numerical models validated against small-amplitude dynamic centrifuge tests - Ge Cui; Alec M. Marshall; Charles M. Heron; Liyao Wan (Soil Dynamics and Earthquake Engineering, 2025)

Corrigendum to “Ecosystem sustainability of rice and aquatic animal co-culture systems and a synthesis of its underlying mechanisms” [Science of the Total Environment, 880 (2023) 163314] - Lei Ge; Yu Sun; Yujie Li; Luyao Wang; Guanqing Guo; Lili Song; Cui Wang; Guogan Wu; Shuangxi Li; Peng Li (Science of The Total Environment, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Dam construction and nutrient enrichment led to simplification of riverine micro-food webs by weakening top-down control effect - Ge Cui; Juan Chen; Chao Wang; Peifang Wang; Bo Zhang; Shunqing Zhang; Qihao Nie (Journal of Environmental Management, 2025)

The influence of differently aged microplastics on electrochemical degradation efficiency - Ran Chen; Yining Deng; Jinyan Wang; Yuchun Cui; Yuzeng Zhao; Honghua Ge (Journal of Environmental Management, 2025)

Polyphenol coacervate-derived bioadhesive glue with mussel-mimicking secretion behavior for treating chemotherapy-induced oral mucositis - Ning Wang; Mengqi Liu; Hanru Liu; Jiwei Cui; Shaohua Ge; Jianhua Li (Chemical Engineering Journal, 2025)

Hierarchical hollow P-doped ZIF-8/MXene aerogel composites for phase change materials integrating shape stability, thermal energy storage, solar-thermal conversion and flame retardancy - Huiqi Gao; Haiyun Ma; Jinjin Cui; Xusheng Ge; Jiajun Tan; Jianzhong Xu (Chemical Engineering Journal, 2025)

Cutting Efficiency and Microdamage in Hard Rocks Under Repeated Abrasive Water Jet Cutting - Zhe Zhou; Zhi Yao; Zhaolong Ge; Zhongtan Li; Jianming Shangguan; Yuhuai Cui; Binbin Ge; Qinglin Deng (Rock Mechanics and Rock Engineering, 2025)

Improvement and Recovery of Intestinal Flora Disorder Caused by Ciprofloxacin Using Lactic Acid Bacteria - Xiumin Su; Li Su; Mengyuan Cao; Yulu Sun; Jinghan Dai; Yuanjie He; Wei Li; Wupeng Ge; Xin Lv; Qiang Zhang; Shenghui Cui; Jia Chen; et al. (Probiotics and Antimicrobial Proteins, 2025)

The Association of Cadmium Exposure and Anthropometrics in School-Age Children: A Longitudinal Study - Meng Wu; Linhong Li; Tianwenjing Huang; Jieying Gao; Peng Gan; Shudan Liu; Dan Wu; Siyan Ye; Chengpeng Cui; Longjie Li; Ge Yan; Qin Liu (Biological Trace Element Research, 2025)

Isolation and Identification of Metanophrys sinensis from Shrimps (Litopenaeus vannamei) and Screening of Chinese Herbal Medicines for Its Control - Mingfeng Ge; Yifan Xu; Juan Feng; Zheng Liang; Hao Cui; Xinxin Jiang; Jianping Wang; Shengwei Xu; Rongrong Ma (Fishes, 2025)
The parasitic disease scuticociliatosis poses significant economic losses to shrimp culture. In this study, an unidentified species of ciliates was discovered in Litopenaeus vannamei. Morphological and molecular analyses were conducted to identify the parasite species, while a reinfection experiment was performed to assess its virulence towards L. vannamei. Simultaneously, Chinese herbal medicine was assessed for potential prevention and control of this pathogen. The results revealed that the SSU rDNA (93.87%), LSU rDNA (98.20%), and ITS1-5.8S-ITS2 rDNA (87.10%) genes exhibited high homology with Metanophrys sinensis, suggesting its classification within the genus Metanophry sp. The reinfection experiment demonstrated median lethal dosages of 6638 individuals/mL at 24 h and 4658 individuals/mL at 48 h for this ciliate on the host L.vannamei. In terms of drug control, we conducted a screening of 23 Chinese herbal extracts through in vivo injection trials and observed that Mume fructus extract exhibits potent biocidal activity. Specifically, the M. fructus extract solution with a final concentration of 5 mg/mL (0.5% v/v) eliminated all ciliates within 3 h. In conclusion, this study identified the ciliate parasite as Metanophrys sinensis and demonstrated its virulence to Litopenaeus vannamei. Mume fructus extract was found to effectively control the parasite, offering potential for managing scuticociliatosis in shrimp culture.

Numerical Analysis of a Vertical Axis Wind Turbine with Racetrack Trajectory - Sixiong Ge; Yan Yan; Zhecheng Lou; Jie Xu; Zhehao Sheng; Jiahuan Cui (Journal of Marine Science and Engineering, 2025)
This study presents a comprehensive numerical and theoretical analysis comparing the aerodynamic performance of a racetrack trajectory vertical axis wind turbine with a baseline VAWT. The racetrack trajectory comprises two parallel straight segments connected by semicircular arcs. However, two critical research gaps remain: the aerodynamic performance of this non-axisymmetric rotor, especially its sensitivity to inflow direction, is not well understood, and a computationally efficient theoretical model for its rapid design is lacking. Using unsteady Reynolds-Averaged Navier–Stokes (URANS) simulations to systematically quantify this sensitivity, and developing an adapted double multiple streamtube (DMST) model, the performance of both turbines is evaluated across tip speed ratios (TSRs) of 1.5–4 and inflow angles β = 0–90°. Results indicate that the racetrack turbine achieves a peak power coefficient of 0.49 at TSR = 2.5 and β = 90°, 16.7% higher than the baseline VAWT. Its performance is highly sensitive to inflow direction, whereas the baseline operates more uniformly across angles. Flow field and wake analyses reveal that the racetrack turbine exhibits faster wake recovery and lower turbulence intensity downstream under optimal inflow. This study demonstrates the potential of racetrack turbines for enhanced directional efficiency in marine wind conditions and validates the adapted DMST model as a reliable tool for preliminary design.

Rapid and efficient stem segment regeneration propagation system for Euonymus bungeanus - Kai-Ge Cui; Hao-Lin Wang; Wen-Yue Quan; Zhuo-Zhuo Ye; Cheng-Ri Zhao (South African Journal of Botany, 2025)

Parental permethrin exposure disrupts offspring metabolism via microbiota–tryptophan axis and is rescued by Lactobacillus plantarum Y1 - Jie Lin; Zexiu Qi; Ge Wang; Jusheng Zheng; Leqi Cui; Ye Peng; Quancai Sun (Journal of Hazardous Materials, 2025)

Decoding soil resilience: The role of eco-corona in alleviating toxicity for aged tire wear particles and benzalkonium chloride (C12) co-exposure - Bei Jiang; Yunhong Pu; Shengnan Shi; Zhaobo Chen; Dongxue Hu; Hui Ge; Shiming Cui; Yifan Wang; Pengcheng Zhang; Zihan Wang (Journal of Hazardous Materials, 2025)

Chlorine-anion doping enhances the metal-oxygen covalency of Bi0.5Sr0.5FeO3-δ air electrode: achieving superior catalytic activity for reversible solid oxide cells - Hui Ye; Zhipeng Miao; Yanfeng Fu; Pengkai Shan; Bin Qian; Lin Ge; Han Chen; Yifeng Zheng; Sheng Cui (Chemical Engineering Journal, 2025)

Fluorinated poly(alkoxide magnesium) electrolyte derived favorable electrodes-electrolyte interphases enable high-temperature magnesium metal batteries - Gaohao Sun; Zhilin Yang; Xuesong Ge; Shu Zhang; Jinlei Zhang; Mingao Chen; Qingyun Liu; Guanglei Cui (Chemical Engineering Journal, 2025)

Impact of Jet Pressure and Ice Temperature on Erosion Pit Formation During Water Jet Ice-breaking - Zhaolong Ge; Xuanyi Chen; Binbin Ge; Qinglin Deng; Rongzheng Ge; Jinming Cui (Rock Mechanics and Rock Engineering, 2025)

Mechanisms of thermal, acid, desiccation and osmotic tolerance of Cronobacter spp. - Yanfei Yan; Mengyuan Cao; Jiaqi Ma; Jia Suo; Xiaobao Bai; Wupeng Ge; Xin Lü; Qiang Zhang; Jia Chen; Shenghui Cui; Baowei Yang (Critical Reviews in Food Science and Nutrition, 2025)

The Identification and Synthesis of New Sea Cucumber Peptides Leveraging Peptidomics Technology, along with their Anti-Parkinson’s Disease Efficacy - Jiawei Liu; Yusheng Shi; Lingling Jin; Baixue Sun; Ruonan Wang; Guangbo Ge; Guanghao Zhu; Xiaolin Cui; Jie Zhao; Yan Zhang; Sheng Li (Journal of Neuroimmune Pharmacology, 2025)

Multitree genetic programming with spherical-based operators for synthetic minority over-sampling technique in unbalanced data - Yuyang Cui; Ziliang Du; Hongwei Ge; Guangyu Zou; Yaqing Hou (Swarm and Evolutionary Computation, 2025)

Pollen-vegetation-climate relationships in different steppe types of North China: implications for Quaternary reconstructions of vegetation and climate - Yongjie Zhao; Fan Xu; Sidan Cui; Xin Mao; Gaolei Jiang; Ruchun Zhang; Linjing Liu; Yawen Ge; Yuecong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Simultaneously sampling sulfonamide antibiotics (SAs) and endocrine disrupting chemicals (EDCs) in aqueous environment by the DGT passive sampler with a novel composite binding gel - Jing Wang; Peng Zhang; Wenjun Chen; Yaqing Cui; Linke Ge; Yinping Hou (Journal of Environmental Chemical Engineering, 2025)

Morphology and community structure characteristics of aerobic granular sludge: A review - Peixin Liu; Yue Yang; Ma Ge; Qinghui Luo; Bin Cui; Han Cui; Tingting Cao; Dandan Zhou (Journal of Environmental Chemical Engineering, 2025)

Z-scheme Ag2MoO4/g-C3N4 heterojunction photocatalysts for sulfadiazine degradation under sunlight irradiation - Huanbo Ni; Xuejun Zou; Yuying Dong; Jun Ke; Hui Ge; Yubo Cui (Journal of Environmental Chemical Engineering, 2025)

Dynamically cross-linked polyethylene vitrimers: An alternative approach to high-performance high-voltage cable insulation - Zhuolin Zhang; Kangning Wu; Haoran Sui; Ge Zhao; Youshen Wu; Chenhui Cui; Peng Zhao; Kai Yang; Lisheng Zhong; Baoquan Wan; Shengtao Li; Zhi-Min Dang; et al. (Chemical Engineering Journal, 2025)

Organotins as inhibitors targeting human and rat steroid 5α-reductase 1: structure-activity relationship and docking analysis - Shufang Qi; Rong Cui; Wanyu Li; Jin Yang; Ke Zheng; Shaowei Wang; Ren-Shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2025)

The calmodulin-binding transcriptional activator transcription factor family in foxtail millet (Setaria italica L.): Molecular characterization, codon bias, and evolutionary trajectory - Huilong Chen; Kexin Ji; Yun Bai; Yuxian Li; Ying Liu; Fang Liu; Yutong Cui; Weina Ge; Zhenyi Wang (Plant Gene, 2025)

Dual-functional berberine-magnolol co-assembled nanoparticles inhibit Fusarium graminearum growth and mycotoxin production - Chenguo Li; Wei He; Yao Cui; Shimin Wu; Qing'ao Song; Ying Li; Jimin Guo; Xizhen Ge; Pingfang Tian (Pesticide Biochemistry and Physiology, 2025)

Promoting the butterfly transformation of residual sludge: Specific adsorption of heavy metals and in-situ cultivation of granular sludge - Tingting Cao; Qinghui Luo; Peixin Liu; Ma Ge; Liang Liu; Xiyang Fei; Yuanhang Zhao; Bin Cui; Han Cui; Dandan Zhou (Journal of Hazardous Materials, 2025)

Metatranscriptomic insights into nitrogen loss mediated by multi-kingdom microbial interactions in periphytic biofilms under imidacloprid exposure - Zuqiang Cao; Juan Chen; Chao Wang; Peifang Wang; Han Gao; Bingbing Feng; Bo Zhang; Rong Wang; Ge Cui (Journal of Hazardous Materials, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Kinetic stability and transformation pathway of halogenated nitrophenols in drinking water - Jiacheng Ge; Xiaoyan Chen; Zhenqi Du; Yingying Zhou; Ruixin Qu; Jiangdong Cui; Shunke Ding; Wenhai Chu (Journal of Hazardous Materials, 2025)

Visualization study on the effects of water addition on microscopic and macroscopic spray characteristics of methanol with high-pressure direct injection - Qianming Wang; Wuqiang Long; Wei Sang; Guangjie Jin; Zechuan Cui; Ge Xiao; Hua Tian; Jiangping Tian; Yang Wang (Fuel, 2025)

Directional synthesis of high-density aviation fuel through CO2 hydrogenation coupling with naphthalene alkylation over ZnZrOx/Hβ catalyst - Xiaopo Niu; Hongming Qian; Dongyuan Cai; Wenli Zhao; Qingfa Wang; Quanli Ke; Guokai Cui; Chunliang Ge; Lina Tang; Hanfeng Lu (Chemical Engineering Journal, 2025)

Oral administration of nanozyme-armed probiotic Escherichia coli Nissle 1917 with ROS scavenging for inflammatory bowel disease therapy - Tiantian Cui; Bing Li; Zhaoyang Lou; Kai Yang; Kaijin Yan; Danhong Ding; Hong Ge (Chemical Engineering Journal, 2025)

Advance and perspective of carbon-based aerogels and their composites - Yanfeng Fu; Hui Ye; Ke Yuan; Qinxin Wang; Longhui Ge; Sheng Cui (Chemical Engineering Journal, 2025)

Permeability Variations of a Thermal-Treated Granite Fracture Under Constant and Stepwise Cyclic Loadings - Qinglin Deng; Yunlan Bai; Zhaolong Ge; Yongfa Zhang; Yuhuai Cui; Zhi Yao; Shihui Gong; Qisi Huai (Rock Mechanics and Rock Engineering, 2025)

Spatial distribution and genesis of iron, manganese, arsenic, and nitrogen in groundwater of typical areas - Yanyan Li; Xiao Ge; Yifei Du; Hongrui Ding; Xiang Ji; Chuanye Zhou; Yuanyuan Chen; Di Cui; Anhuai Lu (Science China Earth Sciences, 2025)

A practice guideline for therapeutic drug monitoring of mycophenolic acid for solid organ transplants - Shuang Liu; Hongsheng Chen; Zaiwei Song; Qi Guo; Xianglin Zhang; Bingyi Shi; Suodi Zhai; Lingli Zhang; Liyan Miao; Liyan Cui; Xiao Chen; Yalin Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2025)
Mycophenolic acid (MPA), the active moiety of both mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS), serves as a primary immunosuppressant for maintaining solid organ transplants. Therapeutic drug monitoring (TDM) enhances treatment outcomes through tailored approaches. This study aimed to develop an evidence-based guideline for MPA TDM, facilitating its rational application in clinical settings. The guideline plan was drawn from the Institute of Medicine and World Health Organization (WHO) guidelines. Using the Delphi method, clinical questions and outcome indicators were generated. Systematic reviews, Grading of Recommendations Assessment, Development, and Evaluation (GRADE) evidence quality evaluations, expert opinions, and patient values guided evidence-based suggestions for the guideline. External reviews further refined the recommendations. The guideline for the TDM of MPA (IPGRP-2020CN099) consists of four sections and 16 recommendations encompassing target populations, monitoring strategies, dosage regimens, and influencing factors. High-risk populations, timing of TDM, area under the curve (AUC) versus trough concentration ( C 0 ), target concentration ranges, monitoring frequency, and analytical methods are addressed. Formulation-specific recommendations, initial dosage regimens, populations with unique considerations, pharmacokinetic-informed dosing, body weight factors, pharmacogenetics, and drug–drug interactions are covered. The evidence-based guideline offers a comprehensive recommendation for solid organ transplant recipients undergoing MPA therapy, promoting standardization of MPA TDM, and enhancing treatment efficacy and safety.

Advanced performance and operational strategies of partitioned anaerobic membrane bioreactor combined with ferromagnetic biochar for pesticide wastewater treatment at low-temperature and insufficient hydraulic load - Yifan Wang; Liwen Jiang; Dongxue Hu; Bei Jiang; Hui Ge; Shiming Cui; Shuya Zhuang; Jitao Yan; Zihan Wang; Pengcheng Zhang; Zhibo Liang; Zhaobo Chen (Water Research, 2025)

Photocatalytic reduction of hexavalent chromium (Cr(VI)) in water using two-dimensional Fe/Cu-MOF-NH₂ - Shuang Wang; Jie Lu; Qiaozhi Liu; He Cui; Huan Wang; Xiaoqian Feng; Kai Ge; Yongfang Yang; Yonghua Zhao (Journal of Environmental Chemical Engineering, 2025)

Effects of jets interaction and injection strategy on the combustion characteristics in TJI-HPDI methanol engine - Peng Wang; Wuqiang Long; Wentao Zhao; Mingfei Lu; Pengbo Dong; Hua Tian; JingChen Cui; Ge Xiao; Yang Wang; Jianlin Cao (Fuel, 2025)

Use of stable isotopic signatures and fatty acid profiles to authenticate Chinese mitten crab (Eriocheir sinensis) reared in ponds and rice fields - Cui Han; Yujing Xiao; Zhongqi Dai; Lei Feng; Yan Shi; Xiaojie Liu; Jiachun Ge; Jiaxin Yang (Food Control, 2025)

Insight into the environmental photochemistry of nitrated polycyclic aromatic hydrocarbons in water and in ice: kinetics, pathways and photo-modified toxicity - Linke Ge; Siyuan Wang; Nannan Cui; Ziyu Wang; Peng Zhang (Environmental Research, 2025)

Progressively greater temperature sensitivity of organic carbon decomposition in subsoil relative to topsoil along a millennial chronosequence of paddy soils - Xiangxiang Wang; Yi Miao; Jun Cui; Qianru Wang; Ruiqiao Wu; Ze Zhang; Cuiyan Wu; Shuang Wang; Xuebin Xu; Zhaofeng Yuan; Georg Guggenberger; Jianping Chen; et al. (CATENA, 2025)

Effects of MicroRNA-19b Carried by Endothelial Microparticles on the Phenotypic Switching of Vascular Smooth Muscle Cells and the Working Mechanism - Yuxia Cui; Junxian Song; Ting Ge; Manyan Wu; Chongyou Lee; Hong Chen (Bulletin of Experimental Biology and Medicine, 2025)

Dissociation-dependent kinetics and distinct pathways for direct photolysis and •OH/SO4•− radical dominated photodegradation of ionizable antiviral drugs in aquatic systems - Nannan Cui; Linke Ge; Crispin Halsall; Junfeng Niu; Jinshuai Zheng; Peng Zhang (Water Research, 2025)

Effect of seepage flow on face stability for a tunnel in water-rich silty clay overlying sandy cobble strata - Xiaopu Cui; Pengfei Li; Chuang Wang; Zhaoguo Ge; Shaohua Li; Qiguang Di (Tunnelling and Underground Space Technology, 2025)

Relationship between internal metal exposure and thyroid cancer incidence: a case-control study simultaneously validated by BKMR and WQS models - Muke Yu; Jingyu Xun; Yiming Ge; Xinjie Li; Xulong Chen; Lingfei Cui; Xidi Wang; Mingxia Zhang; Zhaomin Xing; Liang Deng; NiJiati AiErken; Shaoyou Lu; et al. (Food and Chemical Toxicology, 2025)

Characteristics of Wintertime Atmospheric PM1 in a Megacity in the Yangtze River Delta, China: A Comparative Study of 2015 and 2022 - Haifeng Meng; Yuanlong Huang; Shiyue Yang; Shijie Cui; Yangzhou Wu; Ning Zhang; Liangyu Feng; Xinlei Ge; Mindong Chen; Junfeng Wang; Eleonora Aruffoa (Aerosol Science and Engineering, 2025)

State augmentation method for multimode nonstationary vibrations of long-span bridges under extreme winds - Simian Lei; Wei Cui; Luca Patruno; Stefano de Miranda; Lin Zhao; Yaojun Ge (Engineering Structures, 2025)

Development of Brassica rapa-nigra monosomic alien addition lines: cytology, genetics, and morphology - Pengfei Li; Haiyan Wu; Shizhen Guo; Shunlin Wang; Mimi Zhang; Mengyang Liu; Wei Ma; Jianjun Zhao; Chen Tan; Cheng Cui; Xianhong Ge; Zaiyun Li (Theoretical and Applied Genetics, 2025)

Global trends in staphylococcus aureus-related lower respiratory infections from 1990 to 2021: findings from the 2021 global burden of disease report - Hong Chen; Shuang Song; Rui Cui; Yong-Wang Feng; Peng Ge (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Global prevalence of Porcine Astrovirus: A systematic review and meta-analysis - Xiaoyu Ge; Yize Li; Feipeng Zhao; Xin’ao Ma; Jiaxuan Li; Yanping Jiang; Wen Cui; Xiaona Wang; Lijie Tang (Preventive Veterinary Medicine, 2025)

The effects of different types of surfactants on the electrochemical degradation of PET microplastics - Ran Chen; Yining Deng; Jinyan Wang; Yuchun Cui; Yuzeng Zhao; Honghua Ge (Journal of Water Process Engineering, 2025)

Integrated learning framework for enhanced specific surface area, pore size, and pore volume prediction of biochar - Chao Chen; Yongjie Hu; Yadong Ge; Junyu Tao; Beibei Yan; Zhanjun Cheng; Xuebin Lv; Xiaoqiang Cui; Guanyi Chen (Bioresource Technology, 2025)

Genetic characterization of coronaviruses causing common cold symptoms based on micro-targeted capture sequencing - Qiao Qiao; Xiaojuan Zhu; Zixinrong Meng; Hongbin Zhang; Tao Wu; Kangchen Zhao; Yiyue Ge; Lunbiao Cui (Archives of Virology, 2025)

Climate change was more important than human activity in late Holocene vegetation change on the southern Tibetan Plateau - Hao Li; Deke Xu; Yong Ge; Yongli Wang; Chang Li; Anning Cui; Yajie Dong; Xinxin Zuo; Can Wang; Naiqin Wu; Houyuan Lu (Quaternary Science Reviews, 2025)

High-resolution sea surface height reconstruction method based on deep learning gradient constraint embedding method - Jifeng Cui; Fangjie Yu; Junwu Tang; Xinglong Zhang; Ge Chen (Ocean Engineering, 2025)

Effects of nozzle inner surface wear on the rock-breaking ability of premixed abrasive water jets - Xiaotian Wang; Zhaolong Ge; Qinglin Deng; Zhi Yao; Yuhuai Cui; Binbin Ge (Ocean Engineering, 2025)

Chemical characterization and classification of vegetable oils using DESI-MS coupled with a neural network - Yiwei Cui; Liangcun Zhu; Yan Li; Kai Ge; Weibo Lu; Lijun Ge; Kang Chen; Jing Xue; Feiyang Zheng; Shuncong Dai; Huafei Pan; Jingjing Liang; et al. (Food Chemistry, 2025)

A novel anaerobic membrane bioreactor with magnetotactic bacteria for organic sulfur pesticide wastewater treatment: Improvement of enzyme activities, refractory pollutants removal and methane yield - Shiming Cui; Dongxue Hu; Zhaobo Chen; Yifan Wang; Jitao Yan; Shuya Zhuang; Bei Jiang; Hui Ge; Zihan Wang; Pengcheng Zhang (Chemical Engineering Journal, 2025)

CO2 emission from soil inorganic C in coastal croplands of the Yangtze Delta - Jun Cui; Ming Nie; Shuang Wang; Zhenke Zhu; Gongle Shi; Yakov Kuzyakov; Tida Ge (Agriculture, Ecosystems & Environment, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Comprehensive source tracing and process supervision of coating industrial wastewater using integrated water quality parameters and fluorescence spectroscopy - Jinlong Yuan; Shiying Chen; Baoxin Ge; Mingyang Cui; Yongjie Wong; Yuanfeng Qi; Yanhong Ge; Aimin Hao; Kai He (Environmental Monitoring and Assessment, 2025)

Adaptive path tracking and control system for unmanned crawler harvesters in paddy fields - Shaocen Zhang; Xinhua Wei; Chengliang Liu; Jinyao Ge; Xinyu Cui; Fei Wang; Anzhe Wang; Wenming Chen (Computers and Electronics in Agriculture, 2025)

Environmental DNA metabarcoding: Current applications and future prospects for freshwater fish monitoring - Shuaishuai Liu; Juan Chen; Ge Cui; Bo Zhang; Bingcheng Yan; Qihao Nie (Journal of Environmental Management, 2025)

Interactions between the co-contamination system of oxcarbazepine-polypropylene microplastics and Chlorella sp. FACHB-9: Toxic effects and biodegradation - Hao Zhang; Baoming Liu; Fengjie Sun; Ziqi Zhang; Yifan Kong; Xiang Liu; Yulin Cui; Yuyang Ma; Yuyong Wu; Jianhua Fan; Baosheng Ge; Yan Cheng; et al. (Journal of Environmental Management, 2025)

Improving the catalytic activity and sintering resistance of Ni-BaCe0.7Zr0.1Y0.1Yb0.1O3−δ cermet anode for ammonia-fueled protonic ceramic fuel cells via Cobalt addition - Bangze Wu; Xiaole Yu; Zenan Zhao; Bingyu He; Zhanheng Jin; Zhexiang Yu; Qing Ni; Shoucheng He; Han Chen; Yifeng Zheng; Sheng Cui; Lin Ge (Chemical Engineering Journal, 2025)

Delta Opioid Peptide [d-Ala2, d-Leu5]-Enkephalin Improves Physical and Cognitive Function and Increases Lifespan in Aged Female Mice - Lixia Huo; Hongquan Zhang; Chengwu Tang; Ge Cui; Tao Xue; Huihui Guo; Fandi Yao; Wei Zhang; Wenming Feng (Molecular Neurobiology, 2025)

Pathogenicity comparison between porcine G9P[23] and G5P[23] RVA in piglets - Zixin Li; Yudi Pan; Yanxiang Zhou; Jianshuang Cui; Hailiang Ge; Wei Zhao; Li Feng; Jin Tian (Veterinary Microbiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Moxifloxacin plus Cordyceps polysaccharide ameliorate intestinal barrier damage due to abdominal infection via anti-inflammation and immune regulation under simulated microgravity - Hong-Yun Nie; Jun Ge; Kai-Ge Liu; Yuan Yue; Hao Li; Hai-Guan Lin; Tao Zhang; Hong-Feng Yan; Bing-Xin Xu; Hong-Wei Sun; Jian-Wu Yang; Shao-Yan Si; et al. (Life Sciences in Space Research, 2025)

How do access and spatial dependency shape metro passenger flows - Mengying Cui; Lijie Yu; Shaoyu Nie; Zhe Dai; Ying-en Ge; David Levinson (Journal of Transport Geography, 2025)

Preparation of wood formaldehyde-free adhesive by concentrated water delignification black liquor - Ting Zhang; Jianli Tan; Yongqi Li; Yexuan Tang; Yan He; Yuanyuan Ge; Xuemin Cui (Journal of Cleaner Production, 2025)

Microencapsulation of glutathione through water/oil emulsification and complex coacervation: Improved encapsulation efficiency, physicochemical stability, and sustained release effect - Jingyang Yu; Ge Du; Yishun Yao; Qiuhong Liao; Tong Zhou; Heping Cui; Shahzad Hussain; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Research International, 2025)

Synergistic effect of 2′-Fucosyllactose or galactooligosaccharide with Bifidobacterium bifidum DNG6 improves the intestinal barrier by modulating the SCFAs-TLR4/NF-κB cascade response in DSS-induced colitis in mice - Cui-Cui Sun; Yu-Qi Wang; Xin-Yu Wang; Guo-Fang Zhang; Hong-Fang Cao; Ge Song; Li-Bo Liu; Chun Li; Irina Valeryevna Boyarineva; Peng Du (Food Bioscience, 2025)

Cascading effect modelling of integrating geographic factors in interdependent systems - Yong Ge; Mo Zhang; Rongtian Zhao; Die Zhang; Zhiyi Zhang; Daoping Wang; Qiuming Cheng; Yuxue Cui; Jian Liu (Environmental Modelling & Software, 2025)

Molecularly Engineered NIR-II Emitting Carbon Dots Assemblies for Unprecedented High-Resolution Angiography and Synergistic Photodynamic/Photothermal Tumor Therapy - Xiaokuang Xue; Jian Li; Tiejin Chen; Minhui Cui; Huanyi Liang; Yunxiu Zhang; Mianqi Xue; Haihua Xiao; Jiechao Ge; Pengfei Wang (Chemical Engineering Journal, 2025)

Highly efficient CO2 capture from open air and dilute gas streams by tunable azolate ionic liquids based deep eutectic solvents - Guokai Cui; Yepin Cheng; Wei Zhang; Xiangyu Shen; Lai Li; Ruina Zhang; Yaoji Chen; Quanli Ke; Chunliang Ge; Huayan Liu; Wenyang Fan; Hanfeng Lu (Chemical Engineering Journal, 2025)

Occurrence and ecological risks of organophosphate esters in the sediments of Hangzhou Bay and the East China Sea - Peng Zhang; Yaqing Cui; Ren Shi; Jing Wang; Linke Ge; Qinglin Mu (Marine Pollution Bulletin, 2025)

Photothermal-thermoelectric synergy coupling localized surface plasmon resonance for enhanced flexible photoelectrochemical sensor performance - Mengqi Chen; Hui Tian; Ling Qi; Yuying Zhang; Hongmei Yang; Shenguang Ge; Lina Zhang; Yan Zhang; Lin Li; Kang Cui; Jinghua Yu (Chemical Engineering Journal, 2025)

Enhanced removal of phenolic contaminants with permanganate oxidation mediated by SiO2@TEMPO: Performance, transformation pathway, and selectivity - Xiaoyan Chen; Jiangdong Cui; Xinyu Yang; Taoyue Yuan; Jiacheng Ge; Mengtao Ma; Shunke Ding; Wenhai Chu (Chemical Engineering Journal, 2025)

A Comprehensive Assessment of Water Loss and Driving Forces for the Middle Route of the South-to-North Water Diversion Project from Humanistic Perspective - Jinyu Xiao; Quansheng Ge; Ming Hu; Huijuan Cui (Water Resources Management, 2025)

An automatic method for extracting sand dunes based on slope cost distance from digital elevation models - Meirui Ge; Fayuan Li; Junfei Ma; Fangyuan Yu; Lingzhou Cui (Advances in Space Research, 2025)

Intelligent cooperative control for flexible landing on small celestial bodies - Pingyuan Cui; Dongyue Zhao; Zelong Chen; Dantong Ge; Jiateng Long (Advances in Space Research, 2025)

An overview on the legacy and risks of Polychlorinated Biphenyls (PCBs) and Organochlorinated Pesticides (OCPs) in the polar regions - Peng Zhang; Jing Wang; Andrew Sweetman; Linke Ge; Rongguang Xing; Hao Ji; Jingfeng Yan; Qian Xiao; Yaqing Cui; Hongrui Ma; Sisi Xu (Marine Pollution Bulletin, 2024)

Monoclonal antibody development and antigenic epitope identification of infectious bursal disease virus VP5 - Jinze Han; Xinxin Niu; Chengfei Ge; Ziwen Wu; Guodong Wang; Mengmeng Huang; Yulong Zhang; Runhang Liu; Mengmeng Xu; Hangbo Yu; Jingzhe Han; Suyan Wang; et al. (The Veterinary Journal, 2024)

Association of ambient ozone exposure with early cardiovascular damage among general urban adults: A repeated-measures cohort study in China - Qiyou Tan; Min Zhou; Xiaojie You; Jixuan Ma; Zi Ye; Wendi Shi; Xiuqing Cui; Ge Mu; Linling Yu; Weihong Chen (Science of The Total Environment, 2024)

Analysis on pollutants removal and sludge characteristics of a novel two-phase anaerobic/aerobic/integrated deoxygenated and anoxic reactor associated with membrane process for treating pesticide wastewater - Shuya Zhuang; Zhaobo Chen; Zhibo Liang; Dongxue Hu; Hui Ge; Bei Jiang; Jian Dong; Fei Han; Jitao Yan; Yifan Wang; Shiming Cui (Science of The Total Environment, 2024)

A 2D/3D hierarchical hybrid enables energy-saving hydrogen production coupled with glycerol and urea electro-oxidation - Ziyu Zhou; Fenghua Ge; Ruirui Xu; Xu Dong; Mengjiao Guo; Guanwei Cui; Qian Wang; Pin Hao (Journal of Environmental Chemical Engineering, 2024)

Use of proteomics to elucidate characteristics of Cronobacter sakazakii under mild heat stress - Yanfei Yan; Mengyuan Cao; Jiaqi Ma; Jia Suo; Xiaobao Bai; Wupeng Ge; Xin Lv; Qiang Zhang; Jia Chen; Shenghui Cui; Baowei Yang (International Journal of Food Microbiology, 2024)

Comparative evaluating laser ionization and iKnife coupled with rapid evaporative ionization mass spectrometry and machine learning for geographical authentication of Larimichthys crocea - Weibo Lu; Honghai Wang; Lijun Ge; Siwei Wang; Xixi Zeng; Zhujun Mao; Pingya Wang; Jingjing Liang; Jing Xue; Yiwei Cui; Qiaoling Zhao; Keyun Cheng; et al. (Food Chemistry, 2024)

A novel and cost-effective biological denitrification associated with membrane process for treating pesticide wastewater: Excellent nitrogen removal effect and higher environment benefits - Shuya Zhuang; Dongxue Hu; Zhaobo Chen; Zhibo Liang; Junzhe Song; Hui Ge; Bei Jiang; Jian Dong; Fei Han; Jitao Yan; Yifan Wang; Shiming Cui (Desalination, 2024)

Iron Metabolism and Ferroptosis in Early Brain Injury after Subarachnoid Haemorrhage - Shihao Ge; Ziwen Jing; Lele Wang; Xiaocong Cui; Xin Zhang; Xiaopeng Wang (Molecular Neurobiology, 2024)
At present, it appears that the prognosis for subarachnoid haemorrhage (SAH), which has a high death and disability rate, cannot be greatly improved by medication or other treatment. Recent research suggests that different types of cell death are implicated in early brain injury (EBI) after SAH, and this has been recognised as a major factor impacting the prognosis of SAH. Ferroptosis, which is a recently identified imbalance of iron metabolism and programmed cell death triggered by phospholipid peroxidation, has been shown to be involved in EBI after SAH and is thought to have a significant impact on EBI. The decomposition of cleaved haemoglobin during SAH involves the release of enormous amounts of free iron, resulting in iron metabolism disorders. Potential therapeutic targets for the signalling pathways of iron metabolism disorders and ferroptosis after SAH are constantly being discovered. To serve as a guide for research into other possible therapeutic targets, this paper will briefly describe the mechanisms of dysregulated iron metabolism and ferroptosis in the pathogenesis of SAH and highlight how they are involved in the development and promotion of EBI in SAH.

Helicid Alleviates Neuronal Apoptosis of Rats with Depression-Like Behaviors by Downregulating lncRNA-NONRATT030918.2 - Yuan Zhang; Zhen-Yi Jiang; Mei Wang; Xiao-Tong Zhang; Peng Ge; Wei Wang; Yuan-Xiang Zhang; Jiu-Cui Tong (Molecular Neurobiology, 2024)

Tripartite-motif 3 represses ovarian cancer progression by downregulating lactate dehydrogenase A and inhibiting AKT signaling - Yu Cong; Xin Cui; Yaqian Shi; Xinxing Pan; Ke Huang; Zhe Geng; Pengfei Xu; Lili Ge; Jin Zhu; Juan Xu; Xuemei Jia (Molecular and Cellular Biochemistry, 2024)

Efficient RNA interference method by feeding in Brachionus plicatilis (Rotifera) - Yu Zhang; Dongqi Kan; Yang Zhou; Hairong Lian; Lingling Ge; Jing Shen; Zhongqi Dai; Yan Shi; Cui Han; Xiaojie Liu; Jiaxin Yang (Biotechnology Letters, 2024)

Soil bacterial and protist communities from loquat orchards drive nutrient cycling and fruit yield - Li Wang; Jianhong Ji; Fei Zhou; Bibo Wu; Yingying Zhong; Lin Qi; Miao Wang; Yuping Wu; Xintao Cui; Tida Ge; Zhenke Zhu (Soil Ecology Letters, 2024)

Estimating the spatiotemporal distribution of PM2.5 concentrations in Tianjin during the Chinese Spring Festival: Impact of fireworks ban - Zhifei Liu; Kang Zheng; Shuai Bao; Yide Cui; Yirong Yuan; Chengjun Ge; Yixuan Zhang (Environmental Pollution, 2024)

Identifying modifiable factors and their joint effect on frailty: a large population-based prospective cohort study - Ling-Zhi Ma; Yi-Jun Ge; Yi Zhang; Xi-Han Cui; Jian-Feng Feng; Wei Cheng; Lan Tan; Jin-Tai Yu (GeroScience, 2024)

Anaerobic degradation of pesticide wastewater: Improving sludge characteristics and reducing membrane fouling with combined tandem UASB+membrane system with high velocity settlers - Jitao Yan; Zhaobo Chen; Dongxue Hu; Hui Ge; Bei Jiang; Jian Dong; Fei Han; Shuya Zhuang; Zhibo Liang; Yifan Wang; Shiming Cui (Water Research, 2024)

Influence of soil N availability on priming effects depending on temperature - Jun Cui; Liang Wei; Zhenke Zhu; Yangwu Deng; Song Chen; Yakov Kuzyakov; Tida Ge (Soil and Tillage Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Optimization of ethylene thiourea, cyanide, and heavy metals removal and gas production enhancement in organosulfur pesticide wastewater using ferromagnetic biochar in anaerobic membrane bioreactor - Yifan Wang; Zhaobo Chen; Dongxue Hu; Liwen Jiang; Shiming Cui; Shuya Zhuang; Jitao Yan; Jian Dong; Fei Han; Bei Jiang; Hui Ge; Zhibo Liang (Chemical Engineering Journal, 2024)

Causes and dynamic change characteristics of the 2022 devastating floods in Pakistan - Huayong Chen; Jiang Xiong; Peng Cui; Xiaoqing Chen; Yonggang Ge; Congxi Fang; Bo Zhang; Tao Yang; Inamullah Khan (Natural Hazards, 2024)

Monitoring nonlinear large gradient subsidence in mining areas through SBAS-InSAR with PUNet and Weibull model fusion - Yuanjian Wang; Ximin Cui; Chunqing Ge; Yuhang Che; Yuling Zhao; Peixian Li; Yue Jiang; Xiaoqing Han (Environmental Science and Pollution Research, 2024)

Heterologous synthesis of ginsenoside F1 and its precursors in Nicotiana benthamiana - Qin Chen; Jun Lei; Xiaolei Li; Jinyu Zhang; Diqiu Liu; Xiuming Cui; Feng Ge (Journal of Plant Physiology, 2024)

Forecasting daily PM2.5 concentrations in Wuhan with a spatial-autocorrelation-based long short-term memory model - Zhifei Liu; Chengjun Ge; Kang Zheng; Shuai Bao; Yide Cui; Yirong Yuan; Yixuan Zhang (Atmospheric Environment, 2024)

Aβ-Aggregation-Generated Blue Autofluorescence Illuminates Senile Plaques as well as Complex Blood and Vascular Pathologies in Alzheimer’s Disease - Hualin Fu; Jilong Li; Chunlei Zhang; Peng Du; Guo Gao; Qiqi Ge; Xinping Guan; Daxiang Cui (Neuroscience Bulletin, 2024)

A computational efficient approach for multi-GNSS real-time precise clock estimation with undifferenced ambiguity resolution - Xiang Zuo; Pan Li; Bobin Cui; Maorong Ge; Harald Schuh (Journal of Geodesy, 2024)

Informal E-waste dismantling activities accelerated the releasing of liquid crystal monomers (LCMs) in Pakistan: Occurrence, distribution, and exposure assessment - Yanhui Ge; Jingren Cui; Lianying Zhang; Shaohan Zhang; Mujtaba Baqar; Zhipeng Cheng (Science of The Total Environment, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

Performance of a novel up-flow electrocatalytic hydrolysis acidification reactor (UEHAR) coupled with anoxic/oxic system for treating coking wastewater - Jian Dong; Zhaobo Chen; Fei Han; Dongxue Hu; Hui Ge; Bei Jiang; Jitao Yan; Shuya Zhuang; Yifan Wang; Shiming Cui; Zhibo Liang (Water Research, 2024)

Endocrine toxicity of atrazine and its underlying mechanisms - Haotang Zhao; Honghao Qian; Jianwei Cui; Zhili Ge; Jingjing Shi; Yingchao Huo; Yuezhu Zhang; Lin Ye (Toxicology, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Oligosaccharide profiles as potential biomarkers for detecting adulteration of caprine dairy products with bovine dairy products - Haiyan Wang; Xiaoying Zhang; Yu Yao; Zhenquan Huo; Xiuxiu Cui; Mengjia Liu; Lili Zhao; Wupeng Ge (Food Chemistry, 2024)

Factors driving antimony accumulation in soil-pakchoi and wheat agroecosystems: Insights and predictive models - Tongliang Wu; Naichi Zhang; Cun Liu; Changfeng Ding; Peng Zhang; Sainan Hu; Yihang Huang; Zixuan Ge; Peixin Cui; Yujun Wang (Environmental Pollution, 2024)

Ionic liquid-based advanced porous organic hyper-crosslinked polymers (ILHCPs) for CO2 capture and conversion - Ruina Zhang; Guokai Cui; Xiuqin Wang; Yinfeng Chen; Xinjie Qiu; Quanli Ke; Dongshun Deng; Chunliang Ge; Hanfeng Lu; Sheng Dai (Chemical Engineering Journal, 2024)

Environmental adaptation, growth performance and nutrient content of the clam Cyclina sinensis from different geographic locations - Shiyu Yan; Qing Xia; Zhenquan Cui; Guoliang Ren; Xiaoying Li; Hongxing Ge; Meimei Liu; Zhiguo Dong (Frontiers in Marine Science, 2024)
The clam Cyclina sinensis is an economically important marine species in China. However, overfishing, habitat destruction, and inbreeding have led to the destruction of genetic resources. In this study, five natural populations [Dandong (DD), Dongying (DY), Tianjin (TJ), Wenzhou (WZ), and Yancheng (YC)] from different geographical locations were relocated and cultured homogeneously to study their potential for translocation and environmental adaptation by observing growth performance and nutrient content. There were significant differences in the growth rates of shell length (SL), shell height (SH), and shell width (SW) among the five populations ( P<0.05 ). The DD, TJ, and YC populations exhibited the highest SL and SH growth rates, whereas these were lowest in the WZ population. The survival rate was highest in the YC population and lowest in the WZ population, which was significantly lower than the other four populations ( P<0.05 ). The DD population exhibited superior plumpness and glycogen content, and the overall glycogen content in male C. sinensis was higher compared with that in females ( P<0.05 ). All populations displayed a high total amino acid content and the essential amino acid/Total Amino Acid (EAA/TAA) and Non-essential amino acid/Total Amino Acid (NEAA/TAA) ratios in the soft tissue of all five populations aligned with the FAO/WHO ideal protein evaluation standards. Despite the same aquaculture environment, however, the nutrient composition of C. sinensis sampled from different populations varied significantly ( P<0.05 ).Therefore, ex situ conservation did not eliminate nutritional differences between the different populations of C. sinensis. These findings highlight the importance of considering environmental and ecological factors in the nutritional assessment and cultivation of shellfish. In addition, C. sinensis from sampling sites closer to the transplantation sites had higher survival rates and growth rates, and the gonadal development of all populations showed adaption to the local environment, resulting in synchronization of the reproductive period.

The effects of microgravity on stem cells and the new insights it brings to tissue engineering and regenerative medicine - Hong-Yun Nie; Jun Ge; Kai-Ge Liu; Yuan Yue; Hao Li; Hai-Guan Lin; Hong-Feng Yan; Tao Zhang; Hong-Wei Sun; Jian-Wu Yang; Jin-Lian Zhou; Yan Cui (Life Sciences in Space Research, 2024)

Exploring the aqueous photodegradation of three ionisable macrolide antibiotics: Kinetics, intermediates and photoinduced toxicity - Linke Ge; Nannan Cui; Crispin Halsall; Yan Yang; Shengkai Cao; Peng Zhang (Journal of Water Process Engineering, 2024)

DEHP induces apoptosis and autophagy of the thyroid via Rap1 signaling pathway: In vivo and in vitro study - Xu Li; Honghao Qian; Hui Ye; Haotang Zhao; Jianwei Cui; Xiaoqi Fang; Zhili Ge; Jingjing Shi; Wen Qi; Lin Ye (Food and Chemical Toxicology, 2024)

Carbon-chain length determines the binding affinity and inhibitory strength of per- and polyfluoroalkyl substances on human and rat steroid 5α-reductase 1 activity - Rong Cui; Lei Ye; Xinyi Qiao; Shaowei Wang; Ke Zheng; Jin Yang; Ren-shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2024)

Di (2-ethylhexyl) phthalate induced lipophagy-related renal ferroptosis in quail (Coturnix japonica) - Yu Zhu; Xiang-Yu Ma; Ling-Ge Cui; Ya-Ru Xu; Chen-Xi Li; Milton Talukder; Xue-Nan Li; Jin-Long Li (Science of The Total Environment, 2024)

Synthesis and antifungal activity of 2,4-diacetylphloroglucinol analogues - Xi-Long Guo; Chun-Yan Zhao; Cui-Ping Zhang; Yi Zhu; Qing-Rong Wu; Yuan-Qing Zhou; Ya-Hong Fei; Fang Ge; Wei Shi (Phytochemistry Letters, 2024)

Numerical investigations of translocation characteristics of nano-silica lunar dust across pulmonary surfactant monolayer - Kailiang Tang; Wen Gao; Dongxing Tao; Bin Wu; Yuan Xue; Haiwen Ge; Xinguang Cui (Environmental Pollution, 2024)

Iron-modified biochar inhibiting Cd uptake in rice by Cd co-deposition with Fe oxides in the rice rhizosphere - Fengfeng Sui; Zhongjun Xue; Kangle Shao; Zikang Hao; Haochuan Ge; Liqiang Cui; Guixiang Quan; Jinlong Yan (Environmental Science and Pollution Research, 2024)

Assessing the performance of winged caisson foundations for offshore wind turbines - Koohyar Faizi; Asaad Faramarzi; Samir Dirar; David Chapman; Ge Cui; Charles M. Heron; Alec M. Marshall (Marine Georesources & Geotechnology, 2024)

Preparation of lanthanum-modified bentonite and its combination with oxidant and coagulant for phosphorus and algae removal - Ge Han; Shenshen Cui; Zheng Fu; Xinshan Song; Xiaohua Chen; Yuhui Wang (Journal of Water Process Engineering, 2024)

Flutter control optimization for a 5000 m suspension bridge with active aerodynamic flaps: a CFD-enabled strategy - Zilong Wang; Lin Zhao; Yiheng Fu; Genshen Fang; Wei Cui; Ke Li; Yaojun Ge (Engineering Structures, 2024)

OsGEX3 affects anther development and improves osmotic stress tolerance in rice - Han Bao; Yuchao Cui; Li Ge; Yan Li; Xiaorong Xu; Ming Tang; Yin Yi; Liang Chen (Planta, 2024)

Variations in life history parameters, population dynamics, and transcriptome regulation of Brachionus plicatilis exposed to triclosan - YunhongYang; Tianyue Mao; Yifan Ding; Lingling Ge; Lei Feng; Meng Cai; Cui Han; Jiaxin Yang (Marine Pollution Bulletin, 2024)

Simulated microgravity altered the gene expression profiles and inhibited the proliferation of Kupffer cells in the early phase by downregulating LMO2 and EZH2 - Jun Ge; Yuan Yue; Hong-Yun Nie; Kai-Ge Liu; Hao Li; Hai-Guan Lin; Tao Zhang; Hong-Feng Yan; Hong-Wei Sun; Jian-Wu Yang; Jin-Lian Zhou; Yan Cui (Life Sciences in Space Research, 2024)

Critical Roles of Surface-Enhanced Heterogeneous Oxidation of SO2 in Haze Chemistry: Review of Extended Pathways for Complex Air Pollution - Zihao Zhang; Haiwei Li; Wingkei Ho; Long Cui; Qihui Men; Li Cao; Yunjiang Zhang; Junfeng Wang; Cheng Huang; Shun-cheng Lee; Yu Huang; Mindong Chen; et al. (Current Pollution Reports, 2024)

A graphene@Cu-MOF hybrid synthesized by mechanical ball milling method and its flame retardancy and smoke suppression effect on EP - Ge Zhang; Weihong Wu; Meng Yao; Yumeng Cui; Yunhong Jiao; Hongqiang Qu; Jianzhong Xu (Chemosphere, 2024)

ATR induces hepatic lipid metabolism disorder in rats by activating IRE1α/XBP1 signaling pathway - Honghao Qian; Yaming Zhao; Yiming Wang; Haotang Zhao; Jianwei Cui; Ziyu Wang; Hui Ye; Xiaoqi Fang; Zhili Ge; Yuezhu Zhang; Lin Ye (Toxicology, 2024)

Impacts of electric field-magnetic powder coupled membrane bioreactor on phenol wastewater treatment: Performance, synergistic mechanism, antibiotic resistance genes, and eco-environmental benefit evaluation - Bei Jiang; Qianzhi Zeng; Qiangwei Liu; Huiying Chai; Jinxun Xiang; Hongxin Li; Shengnan Shi; Aifu Yang; Zhaobo Chen; Yubo Cui; Dongxue Hu; Hui Ge; et al. (Science of The Total Environment, 2024)

Insight into the enhancement effect of humic acid on microbial degradation of triclosan in anaerobic sediments - Juan Chen; Bo Zhang; Chao Wang; Peifang Wang; Ge Cui; Han Gao; Bingbing Feng; Jingjing Zhang (Journal of Hazardous Materials, 2024)

Self-polarization-enhanced oxygen evolution reaction by flower-like core–shell BaTiO3@NiFe-layered double hydroxide heterojunctions - Shuang Wang; Kai Ge; He Cui; Shunli Li; Yongfang Yang; Mingwang Pan; Lei Zhu (Chemical Engineering Journal, 2024)

Construction of IO-B-TiO2/In2O3 S-scheme heterojunction with photothermal effects and its highly efficient photocatalytic reduction of CO2 under full-spectrum light - He Cui; Jiayu Cao; Yi Zhao; Jiabo Wang; Shunli Li; Kai Ge; Jianxin Chen; Yongfang Yang (Chemical Engineering Journal, 2024)

Regulatory mechanism of the miR172e–LbrAP2 module during the vegetative growth phase transition in Lilium - Junting Feng; Yiqing Wang; Wei Ge; Kezhong Zhang; Jinteng Cui (Planta, 2024)

Machine learning-guided REIMS pattern recognition of non-dairy cream, milk fat cream and whipping cream for fraudulence identification - Yiwei Cui; Weibo Lu; Jing Xue; Lijun Ge; Xuelian Yin; Shikai Jian; Haihong Li; Beiwei Zhu; Zhiyuan Dai; Qing Shen (Food Chemistry, 2023)

Chitosan-based molecularly imprinted sponge for selective recognition and recycling of dibenzothiophene from diesel - Yan Huang; Ge Niu; Jie Zhu; Haiyan Ji; Linhua Zhu; Mingqing Hua; Yanhong Chao; Peng Cui; Wenshuai Zhu (Chemical Engineering Journal, 2023)

A Sedentary Lifestyle Changes the Composition and Predicted Functions of the Gut Bacterial and Fungal Microbiota of Subjects from the Same Company - Longwei Xu; Wenkun Li; Lu Ling; Ziran Zhang; Zilu Cui; Jiang Ge; Yun Wang; Qianlong Meng; Yadan Wang; Kuiliang Liu; Jun Zhou; Fanxin Zeng; et al. (Current Microbiology, 2023)
A sedentary lifestyle affects the diversity and composition of the gut microbiota, but previous studies have mainly focused on bacteria instead of fungi. Here, we compared both the fecal bacterial and fungal microbiota compositions and functions in sedentary persons and controls. Subjects from the China Railway Corporation, including 99 inspectors and 88 officials, were enrolled in our study. Fecal microbiota communities were analyzed using 16S rRNA gene sequencing for bacteria and ITS sequencing for fungi. We found that the diversity of the gut microbiota of the sedentary group was significantly lower than that of the control group ( P < 0.05). The sedentary group had a higher abundance of Firmicutes, a lower abundance of Actinobacteria and Proteobacteria and a higher abundance of Ascomycota, and a lower abundance of Basidiomycota. Furthermore, functional prediction analysis of the fungal microbiota revealed more L-tryptophan degradation to 2-amino-3-carboxymuconate semialdehyde, more phospholipid remodeling (phosphatidylethanolamine, yeast), and more L-tyrosine degradation I, as well as less pentose phosphate pathway (non-oxidative branch), less adenosine nucleotide biosynthesis and less L-valine biosynthesis in the sedentary group ( P < 0.05). Thus, a sedentary lifestyle changes the composition and function of the gut microbiota. It may change the pentose phosphate pathway (non-oxidative branch), nucleic acid and amino acid biosynthesis and phospholipid metabolism in fungi.

Tracing the origin of Taiping Houkui green tea using 1H NMR and HS-SPME-GC–MS chemical fingerprints, data fusion and chemometrics - Ge Jin; Yuanyuan Zhu; Chuanjian Cui; Chen Yang; Shaode Hu; Huimei Cai; Jingming Ning; Chaoling Wei; Aoxia Li; Ruyan Hou (Food Chemistry, 2023)

Rapid discrimination of Anji Baicha origin using field-portable spectroradiometer - Ge Jin; Xiang Gui; Yuanyuan Zhu; Delong Zhan; Xinjie Du; Xing Du; Xin Zhang; Yan Zhou; Chuanjian Cui; Chao Zhuo; Xiaochun Wan; Ruyan Hou (Food Control, 2023)

Efficient production of biosurfactant surfactin by a newly isolated Bacillus subtilis (sp.) 50499 strain from oil-contaminated soil - Yulu Du; Yue Wang; Tianyou Cui; Lianpeng Ge; Fan Yu; Mengqian Zhao; Qihang Xu; Mingjie Jin; Bo Chen; Xuwei Long (Food and Bioproducts Processing, 2023)

Study of filtration, digestion and absorption of Chlorella pyrenoidosa by juvenile Chinese mitten crab (Eriocheir sinensis) - Jiancheng Zeng; Jian Tian; Dongqi Kan; Cui Han; Xiaoqing Fei; Xingkong Ma; Zhihong Wang; Weijian Shen; Jiaxin Yang; Jiachun Ge (Aquaculture, 2023)

Experimental study on Diels-Alder addition of conjugated dienes directly from cracking C5 fraction by continuous micro-channel reactors - Zehao Jing; Tingting Ge; Hui Guo; Yuchao Li; Zhou Li; Cuncun Zuo; Ming Wang; Haofei Huang; Lin Guo; Guangjun Cui (Fuel, 2023)

Comprehensive investigation of milk oligosaccharides in different mammalian species and the effect of breed and lactation period on sheep milk oligosaccharides - Haiyan Wang; Minghui Zhang; Yucui Huo; Xiuxiu Cui; Rui He; Bei Han; Zhongfu Wang; Yuxuan Song; Xin Lv; Jing Zhang; Wupeng Ge (Food Research International, 2023)

Genomic characterization and phylogenetic analysis of Aleutian mink disease virus identified in a sudden death mink case - Xingyang Cui; Yan Yang; Fang Wang; Jilong Luo; Ping Zhang; Hongyan Chen; Lili Zhao; Junwei Ge (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Multi-GNSS precise point positioning with predicted orbits and clocks - Longjiang Tang; Jungang Wang; Bobin Cui; Huizhong Zhu; Maorong Ge; Harald Schuh (GPS Solutions, 2023)
Global Navigation Satellite Systems (GNSS) Real-time Precise Point Positioning (RT-PPP) strongly relies on the precise satellite orbits and clocks, especially the latter requires high update rate, e.g., five seconds, due to its limited prediction accuracy. Such a high-rate update frequency is a burden to both the data analysis and communicating, and interruption in communicating is almost unavoidable. For the new constellations such as Galileo and BDS-3 with high-stability hydrogen clocks onboard, it is possible to predict satellite clocks to a longer arc. Moreover, recent developments in multi-GNSS ultra-rapid precise orbit determination enables the half-hourly update, ensuring the availability with a prediction arc of 30–60 min. We investigate multi-GNSS RT-PPP using half-hourly predicted products and demonstrate that a 3-D accuracy of 2.9 and 11.3 cm can be achieved for static and simulated kinematic solutions, respectively. We present the different clock prediction accuracies of different types of satellites and propose a satellite-specific weighting strategy in PPP, which exploits the benefits of the satellites of good performance. The method is based on the prediction accuracy of both, satellites and clocks, and shows an improvement of 15 to 60% compared to those without satellite-specific weighting or with simplified weighting strategies. We also demonstrate that Galileo satellites contribute the most in the quad-constellation solution, thanks to the highly stable satellite clocks.

Cropland expansion delays vegetation spring phenology according to satellite and in-situ observations - Guosong Zhao; Jinwei Dong; Jilin Yang; Huanjiong Wang; Junhu Dai; Yan Zhou; Yaoping Cui; Quansheng Ge (Agriculture, Ecosystems & Environment, 2023)

“Mini-community” simulation revealed the differences of endophytic fungal communities between the above- and below-ground tissues of Ephedra sinica Stapf - Xi Liu; Jin-Long Cui; Zhong-Ya Zhou; Zong-Bao Zhang; Xuan-Ge Cui; Bo Han; Jun-Hong Wang; Meng-Liang Wang; Yi-Min Li (Fungal Biology, 2023)

Unveiling innovative design of customizable adhesive flexible devices from self-healing ionogels with robust adhesion and sustainability - Yapeng Zheng; Tianyang Cui; Jingwen Wang; Hua Ge; Zhou Gui (Chemical Engineering Journal, 2023)

Insight into wavelength-dependent UVA-LED/chlorine process for micropollutant degradation: Performance, mechanism, and effects of water matrix - Ge Zeng; Jiamin Mai; Linqian An; Cui Huang; Juan Li; Haiping Wang; Qiuhua Li; Jingxin Yang; Xiaolong Xu; Changyu Liu; Jianbo Jia; Tao Yang; et al. (Chemical Engineering Journal, 2023)

The overlooked role of Cr(VI) in micropollutant degradation under solar light irradiation - Tao Yang; Cui Huang; Linqian An; Ge Zeng; Juan Li; Changyu Liu; Xiaolong Xu; Jianbo Jia; Jun Ma (Water Research, 2023)

Metagenome-based analysis of carbon-fixing microorganisms and their carbon-fixing pathways in deep-sea sediments of the southwestern Indian Ocean - Xiao-Lan Yue; Lin Xu; Li Cui; Ge-Yi Fu; Xue-Wei Xu (Marine Genomics, 2023)

Tuning functional ionic deep eutectic solvents as green sorbents and catalysts for highly efficient capture and transformation of CO2 to quinazoline-2,4(1H,3H)-dione and its derivatives - Guokai Cui; Yisha Xu; Daqing Hu; Ying Zhou; Chunliang Ge; Huayan Liu; Wenyang Fan; Zekai Zhang; Biao Chen; Quanli Ke; Yaoji Chen; Bing Zhou; et al. (Chemical Engineering Journal, 2023)

Ecosystem sustainability of rice and aquatic animal co-culture systems and a synthesis of its underlying mechanisms - Lei Ge; Yu Sun; Yujie Li; Luyao Wang; Guanqing Guo; Lili Song; Cui Wang; Guogan Wu; Xiaoyun Zang; Xiaomei Cai; Shuangxi Li; Peng Li (Science of The Total Environment, 2023)

Nonagricultural emissions enhance dimethylamine and modulate urban atmospheric nucleation - Yunhua Chang; Qingyang Ling; Xinlei Ge; Xiangyang Yuan; Shengqian Zhou; Kai Cheng; Jianjiong Mao; Dandan Huang; Qingyao Hu; Jun Lu; Shijie Cui; Yaqing Gao; et al. (Science Bulletin, 2023)

Low-temperature highly selective water delignification based on geopolymer materials - Tao Wang; Jianli Tan; Yan He; Yuanyuan Ge; Xuemin Cui (Bioresource Technology, 2023)

Online chemical characterization of atmospheric fine secondary aerosols and organic nitrates in summer Nanjing, China - Jiukun Xian; Shijie Cui; Xingzhou Chen; Jingyun Wang; Yifan Xiong; Chenjuan Gu; Yuan Wang; Yunjiang Zhang; Haiwei Li; Junfeng Wang; Xinlei Ge (Atmospheric Research, 2023)

Hydrolytic Behavior of Novel Pesticide Broflanilide and Its Dissipative Properties in Different Types of Soils - Yaxin Cui; Shoumeng Wang; Xiaoming Mao; Xupeng Gao; Haonan Ge; Shufan Qu; Xueyang Qiao; Xin Jiang; Jianhua Wang; Guangling Li (Bulletin of Environmental Contamination and Toxicology, 2023)

A new large-area hierarchical PPP-RTK service strategy - Bobin Cui; Xinyuan Jiang; Jungang Wang; Pan Li; Maorong Ge; Harald Schuh (GPS Solutions, 2023)
Introducing precise atmosphere information into precise point positioning enables rapid ambiguity resolution and introduces a significant accuracy improvement. However, it can only be implemented in regions with dense networks and stable communication links. For larger areas, e.g., an intercontinental level, there is a conflict between the accuracy of corrections and the amount of atmosphere information to be disseminated. We develop a hierarchical augmentation mode to combine the advantages of the fitting model and region interpolation model to relieve the communication burden. Relying on the fitting model with fewer coefficients applied over large areas as the essential information, the unmodeled errors are calculated at each reference station, and further correction information is optional compensation depending on the magnitude of the unmodeled residuals. We perform the proposed models on 103 EUREF Permanent Network stations with 200-km station spacing and 84 stations as the external validation. The ionosphere and troposphere fitting models have an average accuracy of about 4.2 and 1.3 cm, respectively, under meteorologically calm conditions. The unmodeled error transmission determined by the magnitude of residuals can be reduced by 61% and 96% for the ionospheric and tropospheric delays, respectively, with respect to the legacy interpolation mode. Further compensation implemented, i.e., unmodeled residuals, can achieve instantaneous convergence for 83.6% of all solutions, and the overall initialization time is within 1.0 min. Thus, the proposed hierarchical positioning mode satisfies real-time positioning convergence requirements and significantly reduces massive corrections in communication.

A review of filamentous sludge bulking controls from conventional methods to emerging quorum quenching strategies - Xin Lu; Ge Yan; Liang Fu; Bin Cui; Jinfeng Wang; Dandan Zhou (Water Research, 2023)

Machine learning applications for identify the geographical origin, variety and processing of black tea using 1H NMR chemical fingerprinting - Chuanjian Cui; Yifan Xu; Ge Jin; Jianfa Zong; Chuanyi Peng; Huimei Cai; Ruyan Hou (Food Control, 2023)

Acacetin attenuates the pancreatic and hepatorenal dysfunction in type 2 diabetic rats induced by high-fat diet combined with streptozotocin - Yu Wang; Lili Liu; Meili Ge; Jingqiu Cui; Xiaoying Dong; Yingqi Shao (Journal of Natural Medicines, 2023)

A self-organizing map approach to the analysis of lake DOM fluorescence for differentiation of organic matter sources - Xincheng Jin; Xiaoqing Chen; Liangmin Gao; Xudong Chen; Juan Ge; Feiyan Wei; Hansong Lu; Yufan Wu; Jiahui Cui; Menghang Yuan (Environmental Science and Pollution Research, 2023)

Concurrent dominant pathways of multifunctional products formed from nocturnal isoprene oxidation - Haiwei Li; Long Cui; Yu Huang; Yunjiang Zhang; Junfeng Wang; Mindong Chen; Xinlei Ge (Chemosphere, 2023)

Dissolved biochar fractions and solid biochar particles inhibit soil acidification induced by nitrification through different mechanisms - Ren-Yong Shi; Ni Ni; Ru-Hai Wang; Jackson Nkoh Nkoh; Xiao-Ying Pan; Ge Dong; Ren-Kou Xu; Xiu-Min Cui; Jiu-Yu Li (Science of The Total Environment, 2023)

Simultaneous carbon dioxide sequestration and nitrate removal by Chlorella vulgaris and Pseudomonas sp. consortium - Qian Yu; Manshuang Yin; Yanrui Chen; Shiqi Liu; Shuo Wang; Yuying Li; Hongli Cui; Daoyong Yu; Baosheng Ge; Fang Huang (Journal of Environmental Management, 2023)

Tuning ionic liquid-based functional deep eutectic solvents and other functional mixtures for CO2 capture - Yisha Xu; Ruina Zhang; Ying Zhou; Daqing Hu; Chunliang Ge; Wenyang Fan; Biao Chen; Yaoji Chen; Wei Zhang; Huayan Liu; Guokai Cui; Hanfeng Lu (Chemical Engineering Journal, 2023)

GhMYB102 promotes drought resistance by regulating drought-responsive genes and ABA biosynthesis in cotton (Gossypium hirsutum L.) - Ruida Liu; Yanhui Shen; Minxuan Wang; Ruihua Liu; Ziqian Cui; Pengzhen Li; Qidi Wu; Qian Shen; Jing Chen; Siping Zhang; Shaodong Liu; Huijuan Ma; et al. (Plant Science, 2023)

Evaluating response mechanisms of soil microbiomes and metabolomes to Bt toxin additions - Lei Ge; Lili Song; Luyao Wang; Yujie Li; Yu Sun; Cui Wang; Jun Chen; Guogan Wu; Aihu Pan; Yunfei Wu; Zhexue Quan; Peng Li (Journal of Hazardous Materials, 2023)

Adsorptive removal of oxytetracycline in wastewater by Cu/Al doped carbon microspheres prepared from low-molecular-weight chitosan - Yan Huang; Leichao Wang; Ge Niu; Mingqing Hua; Linhua Zhu; Peng Cui; Xiaowei Li; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Journal of Environmental Chemical Engineering, 2023)

Development of SSR markers on the basis of the Panax notoginseng transcriptome for agronomic and biochemical trait association analyses - Linlin Su; Yingpeng Zhang; Ye Yang; Yuan Qu; Xiuming Cui; Feng Ge; Diqiu Liu (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Transcriptomics, metabolomics, antioxidant enzymes activities and respiration rate analysis reveal the molecular responses of rice to Cd stress and/or elevated CO2 concentration - Lanlan Wang; Ge Wang; Jinghui Cui; Xuhao Wang; Meng Li; Xiufen Qi; Xuemei Li; Yueying Li; Lianju Ma (Plant and Soil, 2023)

SUMOylation-modified Pelota-Hbs1 RNA surveillance complex restricts the infection of potyvirids in plants - Linhao Ge; Buwei Cao; Rui Qiao; Hongguang Cui; Shaofang Li; Hongying Shan; Pan Gong; Mingzhen Zhang; Hao Li; Aiming Wang; Xueping Zhou; Fangfang Li (Molecular Plant, 2023)

Visualization study on combustion characteristics of direct-injected hydrous methanol ignited by diesel in a constant volume combustion chamber - Qianming Wang; Fuxing Wei; Pengbo Dong; Ge Xiao; Zechuan Cui; Jiangping Tian; Xiuyong Shi; Wuqiang Long (Fuel, 2023)

Extreme wind speed prediction in mountainous area with mixed wind climates - Teng Ma; Wei Cui; Lin Zhao; Ding Yejun; Fang Genshen; Yaojun Ge (Stochastic Environmental Research and Risk Assessment, 2023)

LES-YOLO: A lightweight pinecone detection algorithm based on improved YOLOv4-Tiny network - Mingdi Cui; Yunyi Lou; Yilin Ge; Keqi Wang (Computers and Electronics in Agriculture, 2023)

CO2 methanation over the Ni-based catalysts supported on the hollow ZSM-5 zeolites: Effects of the hollow structure and alkaline treatment - Yan Cui; Bin Chen; Leilei Xu; Mindong Chen; Cai-e Wu; Jian Qiu; Ge Cheng; Ning Wang; Jingxin Xu; Xun Hu (Fuel, 2023)

An anti-salt accumulation 2.5D arch solar-driven evaporator based on Marangoni effect for seawater desalination - Shanshan Luo; Zhili Li; Xuemin Cui; Yuanyuan Ge (Chemical Engineering Journal, 2023)

Dual metal-organic frameworks-derived Fe-atomic sites bounded to fine Fe/Fe C nanoparticles for enhanced oxygen electroreduction - Meixin Chen; Fantao Kong; Heliang Yao; Yafeng Chen; Ge Meng; Ziwei Chang; Chang Chen; Han Tian; Lianzhou Wang; Xiangzhi Cui; Jianlin Shi (Chemical Engineering Journal, 2023)

Blockchain-like E α analysis strategy for two distinct “White-box” modeling methodologies to simulate the incineration of oily sludge - Yuanfeng Qi; Wei Wang; Xiao Quan; Chenxi Fan; Baoxin Ge; Chang Xu; Mingyang Cui; Qinyan Yue; Baoyu Gao; Yue Gao; Kai He (Journal of Cleaner Production, 2023)

CO2 methanation over the Ni-based catalysts supported on nano-CeO2 with varied morphologies - Yufang Bian; Chunying Xu; Xueying Wen; Leilei Xu; Yan Cui; Shuhan Wang; Cai-e Wu; Jian Qiu; Ge Cheng; Mindong Chen (Fuel, 2023)

Isoflurane Preconditioning May Attenuate Cardiomyocyte Injury Induced by Hypoxia/Reoxygenation Possibly by Regulating miR-363-3p - Yanhu Ge; Chengbin Wang; Boqun Cui; Yaguang Liu; Duomao Lin; Liang Zhang; Liyun Zhao; Jun Ma (Neurotoxicity Research, 2022)

Insight into different adsorption behaviors of two fluoroquinolone antibiotics by sediment aggregation fractions - Bo Zhang; Juan Chen; Chao Wang; Peifang Wang; Ge Cui; Jingjing Zhang; Yu Hu; Han Gao (Environmental Science and Pollution Research, 2022)

Genome-wide association study reveals that GhTRL1 and GhPIN8 affect cotton root development - Ziqian Cui; Shaodong Liu; Changwei Ge; Qian Shen; Siping Zhang; Huijuan Ma; Ruihua Liu; Xinhua Zhao; Ruida Liu; Pengzhen Li; Hongchen Wang; Qidi Wu; et al. (Theoretical and Applied Genetics, 2022)

Recent advances in the structure, synthesis, and applications of natural polymeric hydrogels - Khalid Gul; Ren-You Gan; Cui-Xia Sun; Ge Jiao; Ding-Tao Wu; Hua-Bin Li; Ahmad Kenaan; Harold Corke; Ya-Peng Fang (Critical Reviews in Food Science and Nutrition, 2022)

Modeling wide-area tropospheric delay corrections for fast PPP ambiguity resolution - Bobin Cui; Jungang Wang; Pan Li; Maorong Ge; Harald Schuh (GPS Solutions, 2022)
The performance of precise point positioning (PPP) has been significantly improved thanks to the continuous improvements in satellite orbit, clock, and ambiguity resolution (AR) technologies, but the convergence speed remains a limiting factor in real-time PPP applications. To improve the PPP precision and convergence time, tropospheric delays from a regional network can be modeled to provide precise correction for users. We focus on the precise modeling of zenith wet delay (ZWD) over a wide area with large altitude variations for improving PPP-AR. By exploiting the water vapor exponential vertical decrease, we develop a modified optimal fitting coefficients (MOFC) model based on the traditional optimal fitting coefficients (OFC) model. The proposed MOFC model provides a precision better than 1.5 cm under sparse inter-station distances over the Europe region, with a significant improvement of 70% for high-altitude stations compared to the OFC model. The MOFC model with different densities of reference stations is further evaluated in GPS and Galileo kinematic PPP-AR solutions. Compared to the PPP-AR solutions without tropospheric delay augmentation, the positioning precision of those with 100-km inter-station spacing MOFC and OFC is improved by 25.7% and 17.8%, respectively, and the corresponding time to first fix (TTFF) is improved by 36.9% and 33.0% in the high-altitude areas. On the other hand, the OFC model only slightly improves the TTFF and positioning accuracy when using the 200 km inter-station spacing modeling and even degrades the positioning for high-altitude stations, whereas using the MOFC model, the PPP-AR solutions always improve. Moreover, the positioning precision improvement of MOFC compared with OFC is about 22.1%, 21.7%, and 25.7% for the Galileo-only, GPS-only, and GPS + Galileo PPP-AR solutions, respectively.

The spatial and seasonal dependency of daily precipitation extremes on the temperature in China from 1957 to 2017 - Wenhui Chen; Huijuan Cui; Quansheng Ge (International Journal of Climatology, 2022)
The frequency and intensity of extreme precipitation in China increase generally with global warming. It is well‐accepted that higher temperature increases water vapour in the atmosphere, leading to more extreme precipitation events. Assuming relative humidity stay constant, the Clausius–Clapeyron (C–C) relationship indicates that global precipitation extremes increase with temperature at a rate of approximately 7%/°C. This study investigated the dependency of daily precipitation extremes on the temperature using daily data of 525 stations in China during 1957–2017. Results showed that the peak structure and sub C–C scaling (0%/°C–5%/°C) were dominant in China, while the scaling rates exhibited a ‘sub C–C, C–C like or super C–C, negative C–C’ trend from southeast to northwest over China. The upper quartile of precipitation (P75) were more sensitive to temperature change than higher intensities. Unlike the scaling patterns in the whole year, the negative relationships were found dominant in most areas in summer, indicating that as summer's lowest temperature reaches the peak of the year, the negative scaling of extreme precipitation at higher temperatures were reinforced.

Molecular identification and functional verification of SPL9 and SPL15 of Lilium - Mengna Zhao; Rongxiu Liu; Yao Chen; Jinteng Cui; Wei Ge; Kezhong Zhang (Molecular Genetics and Genomics, 2022)

Understanding the Yanshan volcano eruption in the Chaihe–Arxan volcanic field, northeastern China - Xiao-ge Cui; Jian-dong Xu; Hong-mei Yu; Bo Zhao; Wen-jian Yang (Arabian Journal of Geosciences, 2021)

The transcription factor PjERF1 enhances the biosynthesis of triterpenoid saponins in Panax japonicus - Qin Chen; Yilin Yu; Xiang Zhang; Ren Zhao; Jinyu Zhang; Diqiu Liu; Xiuming Cui; Feng Ge (Plant Biotechnology Reports, 2021)

Assessment of potential risks induced by increasing extreme precipitation under climate change - Hefei Huang; Huijuan Cui; Quansheng Ge (Natural Hazards, 2021)

Acrolein Induces Systemic Coagulopathy via Autophagy-dependent Secretion of von Willebrand Factor in Mice after Traumatic Brain Injury - Wenxing Cui; Xun Wu; Dayun Feng; Jianing Luo; Yingwu Shi; Wei Guo; Haixiao Liu; Qiang Wang; Liang Wang; Shunnan Ge; Yan Qu (Neuroscience Bulletin, 2021)
Traumatic brain injury (TBI)-induced coagulopathy has increasingly been recognized as a significant risk factor for poor outcomes, but the pathogenesis remains poorly understood. In this study, we aimed to investigate the causal role of acrolein, a typical lipid peroxidation product, in TBI-induced coagulopathy, and further explore the underlying molecular mechanisms. We found that the level of plasma acrolein in TBI patients suffering from coagulopathy was higher than that in those without coagulopathy. Using a controlled cortical impact mouse model, we demonstrated that the acrolein scavenger phenelzine prevented TBI-induced coagulopathy and recombinant ADAMTS-13 prevented acrolein-induced coagulopathy by cleaving von Willebrand factor (VWF). Our results showed that acrolein may contribute to an early hypercoagulable state after TBI by regulating VWF secretion. mRNA sequencing (mRNA-seq) and transcriptome analysis indicated that acrolein over-activated autophagy, and subsequent experiments revealed that acrolein activated autophagy partly by regulating the Akt/mTOR pathway. In addition, we demonstrated that acrolein was produced in the perilesional cortex, affected endothelial cell integrity, and disrupted the blood-brain barrier. In conclusion, in this study we uncovered a novel pro-coagulant effect of acrolein that may contribute to TBI-induced coagulopathy and vascular leakage, providing an alternative therapeutic target.

Calibrating receiver-type-dependent wide-lane uncalibrated phase delay biases for PPP integer ambiguity resolution - Bobin Cui; Pan Li; Jungang Wang; Maorong Ge; Harald Schuh (Journal of Geodesy, 2021)
Wide-lane (WL) uncalibrated phase delay (UPD) is usually derived from Melbourne–Wübbena (MW) linear combination and is a prerequisite in Global Navigation Satellite Systems (GNSS) precise point positioning (PPP) ambiguity resolution (AR). MW is a linear combination of pseudorange and phase, and the accuracy is limited by the larger pseudorange noise which is about one hundred times of the carrier phase noise. However, there exist inconsistent pseudorange biases which may have detrimental effect on the WL UPD estimation, and further degrade user-side ambiguity fixing. Currently, only the large part of pseudorange biases, e.g., the differential code bias (DCB), are available and corrected in PPP-AR, while the receiver-type-dependent biases have not yet been considered. Ignoring such kind of bias, which could be up to 20 cm, will cause the ambiguity fixing failure, or even worse, the incorrect ambiguity fixing. In this study, we demonstrate the receiver-type-dependent WL UPD biases and investigate their temporal and spatial stability, and further propose the method to precisely estimate these biases and apply the corrections to improve the user-side PPP-AR. Using a large data set of 1560 GNSS stations during a 30-day period, we demonstrate that the WL UPD deviations among different types of receivers can reach ± 0.3 cycles. It is also shown that such kind of deviations can be calibrated with a precision of about 0.03 cycles for all Global Positioning System (GPS) satellites. On the user side, ignoring the receiver-dependent UPD deviation can cause significant positioning error up to 10 cm. By correcting the deviations, the positioning performance can be improved by up to 50%, and the fixing rate can also be improved by 10%. This study demonstrates that for the precise and reliable PPP-AR, the receiver-dependent UPD deviations cannot be ignored and have to be handled.

Effects of different temperatures on seawater acclimation in rainbow trout Oncorhynchus mykiss: osmoregulation and branchial phospholipid fatty acid composition - Jian Ge; Ming Huang; Yangen Zhou; Chengyue Liu; Cui Han; Qinfeng Gao; Yunwei Dong; Shuanglin Dong (Journal of Comparative Physiology B, 2021)

Sources of 24-h personal exposure to PM2.5-bound metals: results from a panel study in Wuhan, China - Xing Wang; Bin Wang; Lili Xiao; Xiuqing Cui; Xingzu Cen; Shijie Yang; Ge Mu; Tao Xu; Min Zhou; Weihong Chen (Environmental Science and Pollution Research, 2021)

Sphingopyxis microcysteis sp. nov., a novel bioactive exopolysaccharides-bearing Sphingomonadaceae isolated from the Microcystis phycosphere - Xiao-ling Zhang; Gui-xian Li; Ya-ming Ge; Nurhezreen Md Iqbal; Xi Yang; Zhen-dong Cui; Qiao Yang (Antonie van Leeuwenhoek, 2021)

Determining the Mineral Admixture and Fiber on Mechanics and Fracture Properties of Concrete under Sulfate Attack - Jin-jun Guo; Kun Wang; Cui-ge Qi (Journal of Marine Science and Engineering, 2021)
The concrete structure in the coastal area suffers from the combined erosion of sulfate and dry–wet cycles. In this study, in order to modify ordinary concrete, fly ash, slag powder, silica fume and polyester fiber are added separately. The crack resistance of concrete was studied through mechanical performance test and three-point bending fracture test of notched beam under sulfate dry–wet cycles. The load-crack opening displacement (P-CMOD) curve characteristics, fracture toughness and fracture energy of modified concrete after corrosion are calculated and analyzed. Results reveal that the P-CMOD curve of modified concrete after corrosion has gone through four stages of damage: initial bending section, proportional elastic section, stable expansion section and softening section. With the increase of dry–wet cycles, the overall corrosion resistance and toughening coefficient of modified concrete increases first and then decreases. Adding 25% fly ash can significantly enhance the fracture toughness of concrete in the initial stage. The addition of polyester fiber and slag is beneficial to the improvement of the instability toughness and fracture energy of the concrete in the later stage.

Aerosol Measurements by Soot Particle Aerosol Mass Spectrometer: a Review - Yunjiang Zhang; Junfeng Wang; Shijie Cui; Dan Dan Huang; Xinlei Ge (Current Pollution Reports, 2020)

Influence of Soil Properties and Aging on Antimony Toxicity for Barley Root Elongation - Peng Zhang; Tong-Liang Wu; Syed Tahir Ata-Ul-Karim; Yuan-Ying Ge; Xu Cui; Dong-Mei Zhou; Yu-Jun Wang (Bulletin of Environmental Contamination and Toxicology, 2020)

Detection and molecular characterization of canine circovirus circulating in northeastern China during 2014–2016 - Lingdi Niu; Zheng Wang; Lili Zhao; Yu Wang; Xingyang Cui; Yunjia Shi; Hongyan Chen; Junwei Ge (Archives of Virology, 2020)

Antioxidative and Probiotic Activities of Lactic Acid Bacteria Isolated from Traditional Artisanal Milk Cheese from Northeast China - Yunjia Shi; Xingyang Cui; Shanshan Gu; Xin Yan; Rui Li; Shuang Xia; Hongyan Chen; Junwei Ge (Probiotics and Antimicrobial Proteins, 2019)

Bifidobacterium bifidum TMC3115 Can Characteristically Influence Glucose and Lipid Profile and Intestinal Microbiota in the Middle-Aged and Elderly - Ke Wang; Xiaohong Yu; Yi Li; Yun Guo; Lin Ge; Fangfang Pu; Xinying Ma; Wenjing Cui; Francesco Marrota; Fang He; Ming Li (Probiotics and Antimicrobial Proteins, 2019)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

A transcriptome analysis uncovers Panax notoginseng resistance to Fusarium solani induced by methyl jasmonate - Diqiu Liu; Qin Zhao; Xiuming Cui; Rui Chen; Xin Li; Bingling Qiu; Feng Ge (Genes & Genomics, 2019)

Morphological characters and molecular data reveal three new species of Fomitopsis (Basidiomycota) - Shun Liu; Chang-Ge Song; Bao-Kai Cui (Mycological Progress, 2019)

Choline, not folate, can attenuate the teratogenic effects ofdibutyl phthalate (DBP) during early chick embryo development - Rui Wang; Da-Guang Sun; Ge Song; Chun Yi Guan; Yi Cui; Xu Ma; Hong-Fei Xia (Environmental Science and Pollution Research, 2019)

A pathogenesis-related protein 10 gene PnPR10–3 was involved in molecular interaction between Panax notoginseng and Fusarium solani - Bifeng Tang; Xin Li; Limei Pu; Qin Zhao; Xiuming Cui; Feng Ge; Diqiu Liu (Australasian Plant Pathology, 2019)

Accelerated Versus Conventional Corneal Collagen Cross-Linking in the Treatment of Keratoconus: A Meta-analysis and Review of the Literature - Yang Jiang; Shan Yang; Ying Li; Ge Cui; Thomas Chengxuan Lu (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Two new Neofomitella species (Polyporaceae, Basidiomycota) based on morphological and molecular evidence - Xing Ji; Dong-Mei Wu; Chang-Ge Song; Shun Liu; Jing Si; Bao-Kai Cui (Mycological Progress, 2019)

Adsorption and Desorption of Carbendazim and Thiamethoxam in Five Different Agricultural Soils - Lingxi Han; Qiqing Ge; Jiajia Mei; Yanli Cui; Yongfei Xue; Yunlong Yu; Hua Fang (Bulletin of Environmental Contamination and Toxicology, 2019)

Evaluation of a traditional method for peak flow discharge estimation for floods in the Wenchuan Earthquake area, Sichuan Province, China - Xiao-jun Guo; Peng Cui; Yong Li; Jin-feng Liu; Yong-gang Ge; Ci-de Wang (Journal of Mountain Science, 2019)

Antibacterial and Antibiofilm Activity of Lactic Acid Bacteria Isolated from Traditional Artisanal Milk Cheese from Northeast China Against Enteropathogenic Bacteria - Xingyang Cui; Yunjia Shi; Shanshan Gu; Xin Yan; Hongyan Chen; Junwei Ge (Probiotics and Antimicrobial Proteins, 2018)

Genomic characterization of circoviruses associated with acute gastroenteritis in minks in northeastern China - Junwei Ge; Shanshan Gu; Xingyang Cui; Lili Zhao; Dexing Ma; Yunjia Shi; Yuanzhi Wang; Taofeng Lu; Hongyan Chen (Archives of Virology, 2018)

Cloning and Characterization of Two MAPK Genes UeKpp2 and UeKpp6 in Ustilago esculenta - Yafen Zhang; Qianwen Ge; Qianchao Cao; Haifeng Cui; Peng Hu; Xiaoping Yu; Zihong Ye (Current Microbiology, 2018)

Tetrandrine Alleviates Nociception in a Rat Model of Migraine via Suppressing S100B and p-ERK Activation in Satellite Glial Cells of the Trigeminal Ganglia - Guangcheng Qin; Bei Gui; Jingmei Xie; Lixue Chen; Lianlian Chen; Zhiwei Cui; Jiying Zhou; Ge Tan (Journal of Molecular Neuroscience, 2018)

Development of Brassica oleracea-nigra monosomic alien addition lines: genotypic, cytological and morphological analyses - Chen Tan; Cheng Cui; Yi Xiang; Xianhong Ge; Zaiyun Li (Theoretical and Applied Genetics, 2017)

Miscanthus sp.: Genetic Diversity and Phylogeny in China - Chunxia Ge; Xiuming Liu; Shimin Liu; Jing Xu; Hongfei Li; Tengteng Cui; Yao Yao; Ming Chen; Weili Yu; Cuixia Chen (Plant Molecular Biology Reporter, 2017)

A rapid and efficient Agrobacterium-mediated transient gene expression system for strawberry leaves and the study of disease resistance proteins - Meng-Yuan Cui; Wei Wei; Kuan Gao; Yin-Ge Xie; Ye Guo; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Identification and genetic characterization of a novel circular single-stranded DNA virus in a human upper respiratory tract sample - Lunbiao Cui; Binyao Wu; Xiaojuan Zhu; Xiling Guo; Yiyue Ge; Kangchen Zhao; Xian Qi; Zhiyang Shi; Fengcai Zhu; Lixin Sun; Minghao Zhou (Archives of Virology, 2017)

The effect of emodin on Staphylococcus aureus strains in planktonic form and biofilm formation in vitro - Xin Yan; Shanshan Gu; Yunjia Shi; Xingyang Cui; Shanshan Wen; Junwei Ge (Archives of Microbiology, 2017)

Artepillin C, is it a good marker for quality control of Brazilian green propolis? - Cui-ping Zhang; Xiao-ge Shen; Jia-wei Chen; Xia-sen Jiang; Kai Wang; Fu-liang Hu (Natural Product Research, 2017)

Impacts of park landscape structure on thermal environment using QuickBird and Landsat images - Xinliang Xu; Hongyan Cai; Zhi Qiao; Liang Wang; Cui Jin; Yaning Ge; Luyao Wang; Fengjiao Xu (Chinese Geographical Science, 2017)

Long-Term Plasticity in Amygdala Circuits: Implication of CB1-Dependent LTD in Stress - Bingjin Li; Tongtong Ge; Ranji Cui (Molecular Neurobiology, 2017)

Neuregulin1β Effects on Brain Tissue via ERK5-Dependent MAPK Pathway in a Rat Model of Cerebral Ischemia–Reperfusion Injury - Ning Gu; Keli Ge; Cui Hao; Yaqing Ji; Hongyun Li; Yunliang Guo (Journal of Molecular Neuroscience, 2017)

Groundwater circulation and hydrogeochemical evolution in Nomhon of Qaidam Basin, northwest China - Yong Xiao; Jingli Shao; Yali Cui; Ge Zhang; Qiulan Zhang (Journal of Earth System Science, 2017)

Branched polymeric prodrug/programmed cell death 4 complexes for combinational cancer therapy - Yu-Jing He; Lei Xing; Peng-Fei Cui; Jia-Liang Zhang; Jian-Bin Qiao; Cheng-Qiong Luo; Ge Jiang; Hu-Lin Jiang (Journal of Pharmaceutical Investigation, 2017)

Trace projection transformation: a new method for measurement of debris flow surface velocity fields - Yan Yan; Peng Cui; Xiaojun Guo; Yonggang Ge (Frontiers of Earth Science, 2016)

The growth and reproduction performance of TALEN-mediated β-lactoglobulin-knockout bucks - Hengtao Ge; Chenchen Cui; Jun Liu; Yan Luo; Fusheng Quan; Yaping Jin; Yong Zhang (Transgenic Research, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Distinct subgenome stabilities in synthesized Brassica allohexaploids - Jiannan Zhou; Chen Tan; Cheng Cui; Xianhong Ge; Zaiyun Li (Theoretical and Applied Genetics, 2016)

Sequence Characteristics and Phylogenetic Implications of the nrDNA Internal Transcribed Spacers (ITS) in Protospecies and Landraces of Sugarcane (Saccharum officinarum L.) - Cui-Feng Yang; Li-Tao Yang; Yang-Rui Li; Ge-Min Zhang; Chun-Ya Zhang; Wei-Zan Wang (Sugar Tech, 2016)

Trends in the prevalence of heart diseases over a ten-year period from single-center observations based on a large echocardiographic database - Hao Lu; Wen-zhi Pan; Quan Wan; Lei-lei Cheng; Xian-hong Shu; Cui-zhen Pan; Ju-ying Qian; Jun-bo Ge (Journal of Zhejiang University-SCIENCE B, 2016)

New norditerpenoid alkaloids from Aconitum vilmorinianum Komarov - Cui-Ling Chen; Wen-Hong Tan; Yan Wang; Zhi-Ge Xue; Chun-Ping Wan; Zhu-Ya Yang; Zhi-Hong Zhou; Xiao-Xia Ma (Journal of Natural Medicines, 2015)

Concentrations, bioaccumulation, and human health risk assessment of organochlorine pesticides and heavy metals in edible fish from Wuhan, China - Lili Cui; Jing Ge; Yindi Zhu; Yuyi Yang; Jun Wang (Environmental Science and Pollution Research, 2015)

Prediction of surface settlement process based on model shield tunnel driving test - Yong Fang; Zhihao Yang; Ge Cui; Chuan He (Arabian Journal of Geosciences, 2015)

3D-QSAR modeling and molecular docking study on Mer kinase inhibitors of pyridine-substituted pyrimidines - Zhuang Yu; Xianchao Li; Cuizhu Ge; Hongzong Si; Lianhua Cui; Hua Gao; Yunbo Duan; Honglin Zhai (Molecular Diversity, 2015)

Catastrophic debris flows on July 10th 2013 along the Min River in areas seriously-hit by the Wenchuan earthquake - Yong-gang Ge; Peng Cui; Jian-qiang Zhang; Chao Zeng; Feng-huan Su (Journal of Mountain Science, 2015)

Case history of the disastrous debris flows of Tianmo Watershed in Bomi County, Tibet, China: Some mitigation suggestions - Yong-gang Ge; Peng Cui; Feng-huan Su; Jian-qiang Zhang; Xing-zhang Chen (Journal of Mountain Science, 2014)

A strategy for fusion expression and preparation of functional glucagon-like peptide-1 (GLP-1) analogue by introducing an enterokinase cleavage site - Yang Liu; Limei Ren; Lingmiao Ge; Qingxin Cui; Xiaofang Cao; Yuanyuan Hou; Fang Bai; Gang Bai (Biotechnology Letters, 2014)

Serum differential protein identification of Xinjiang Kazakh esophageal cancer patients based on the two-dimensional liquid-phase chromatography and LTQ MS - Cui Li; Guo Xia; Zhang Jianqing; Yang Mei; Bai Ge; Zhang Li (Molecular Biology Reports, 2014)

Overexpression of the AtSTK gene increases salt, PEG and ABA tolerance in Arabidopsis - Lei Bing; Cui-Cui Feng; Jing-Lan Li; Xiao-Xu Li; Bao-Cun Zhao; Yin-Zhu Shen; Zhan-Jing Huang; Rong-Chao Ge (Journal of Plant Biology, 2013)

Rapid development of 36 polymorphic microsatellite markers for Tetranychus truncatus by transferring from Tetranychus urticae - Cheng Ge; Jing-Tao Sun; Yu-Nan Cui; Xiao-Yue Hong (Experimental and Applied Acarology, 2013)

A method to estimate concentrations of surface-level particulate matter using satellite-based aerosol optical thickness - JinHua Tao; MeiGen Zhang; LiangFu Chen; ZiFeng Wang; Lin Su; Cui Ge; Xiao Han; MingMin Zou (Science China Earth Sciences, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Characteristics, causes and mitigation of catastrophic debris flow hazard on 21 July 2011 at the Longda Watershed of Songpan County, China - Yong-gang Ge; Peng Cui; Xiao-jun Guo; Guo-hu Song; Wei-ming Liu (Journal of Mountain Science, 2013)

Serum microRNA expression profile as a biomarker for the diagnosis of pertussis - Yiyue Ge; Kangchen Zhao; Yuhua Qi; Xiaoyan Min; Zhiyang Shi; Xian Qi; Yunfeng Shan; Lan Cui; Minghao Zhou; Yong Wang; Hua Wang; Lunbiao Cui (Molecular Biology Reports, 2013)

Effect of targeted silencing of hTERT mRNA by lentivirus-mediated siRNA on A549 lung cancer cells in vitro - Haibo Tang; Linhu Ge; Wenlong Shao; Yuan Qiu; Dong Cui (Molecular Biology Reports, 2013)

Elevated O3 reduces the fitness of Bemisia tabaci via enhancement of the SA-dependent defense of the tomato plant - Hongying Cui; Yucheng Sun; Jianwei Su; Qin Ren; Chuanyou Li; Feng Ge (Arthropod-Plant Interactions, 2012)

Mapping quantitative trait loci for leaf and heading-related traits in Chinese cabbage (Brassica rapa L. ssp. pekinesis) - Yu Ge; Nirala Ramchiary; Tao Wang; Cui Liang; Na Wang; Zhe Wang; Su Ryun Choi; Yong Pyo Lim; ZhongYun Piao (Horticulture, Environment, and Biotechnology, 2011)

Analysis of phage Mu DNA transposition by whole-genome Escherichia coli tiling arrays reveals a complex relationship to distribution of target selection protein B, transcription and chromosome architectural elements - Jun Ge; Zheng Lou; Hong Cui; Lei Shang; Rasika M Harshey (Journal of Biosciences, 2011)

Episode simulation of Asian dust storms with an air quality modeling system - Cui Ge; Meigen Zhang; Zhiwei Han; Yanju Liu (Advances in Atmospheric Sciences, 2011)

A novel membrane based process to isolate photosystem-I membrane complex from spinach - Jianguo Liu; Mengmeng Yin; Meng Wang; Xuefang Zhang; Baosheng Ge; Shuang Liu; Jianren Lu; Zhanfeng Cui (Photosynthesis Research, 2011)

Characteristics of earthquake-triggered landslides and post-earthquake debris flows in Beichuan County - Jianqi Zhuang; Peng Cui; Kaiheng Hu; Xiaoqing Chen; Yonggang Ge (Journal of Mountain Science, 2010)

Targeting Cholinesterase Inhibitor Poisoning with a Novel Blocker Against Both Nicotinic and Muscarinic Receptors - Wangqian Luo; Xulin Ge; Wenyu Cui; Hai Wang (Neurotoxicity Research, 2010)

Probability assessment of river blocking by debris flow associated with the Wenchuan Earthquake - Jian-Qi Zhuang; Peng Cui; Yong-Gang Ge; Yi-Ping He; Ying-Hui Liu; Xiao-Jun Guo (International Journal of Remote Sensing, 2010)

Sanchi ginseng (Panax notoginseng (Burkill) F. H. Chen) in China: distribution, cultivation and variations - Hong Bo Guo; Xiu Ming Cui; Na An; Ge Ping Cai (Genetic Resources and Crop Evolution, 2010)

Wet-dry changes in the borderland of Shaanxi, Gansu and Ningxia from 1208 to 1369 based on historical records - Junhu Dai; Quansheng Ge; Shufang Xiao; Mengmai Wang; Wenxiang Wu; Haiting Cui (Journal of Geographical Sciences, 2009)

Soil evolution features of debris flow waste-shoal land - Peng Cui; Yonggang Ge; Jianqi Zhuang; Daojie Wang (Journal of Mountain Science, 2009)

Modeling Impacts of Management on Carbon Sequestration and Trace Gas Emissions in Forested Wetland Ecosystems - Changsheng Li; Jianbo Cui; Ge Sun; Carl Trettin (Environmental Management, 2004)